Data-center expansion and the dynamic regional redistribution of the water-energy-food stress in Texas - Rashed Albatayneh (Resources, Conservation and Recycling, 2027)

Real-time driver activity detection using advanced deep learning models - Md. AL Emran; Md. Ariful Islam; Md. Obaydullahn Khan; Md. Jewel Rana; Saida Tasnim Adrita; Md. Ashik Ahmed; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cognitive Neurodynamics, 2026)

Predicting hydrodesulfurization reactivity of middle distillates for producing ultra-low-sulfur diesel - Xiaoliang Ma; Hamza Albazzaz; Muhieddine A. Safa; Ahmed M. Al-Otaibi; Narjes Ghaloum; Rashed Bouresli; Shibu Jose; Ashraf M. Kamel (Fuel, 2026)

Fatigue assessment of heavy-thick welded T-joint improved by portable pneumatic needle-peening treatment - Xipeng Chen; Naoki Osawa; Sherif Rashed; Takaaki Takeuchi; Donghui Ma; Jun Okada; Masahito Honnami (Engineering Structures, 2026)

Ziziphus spina-christi as a natural feed supplement for sustainable livestock nutrition: An updated narrative review - Youssef A. Attia; Asmaa F. Khafaga; Ayman E. Taha; Islam M. Youssef; Khalid A. Asiry; Adel D. Al-Qurashi; Omer H.M. Ibrahim; Khaled H. El-Kholy; Rashed A. Alhotan; Salem R. Alyileili; Sara H.M. Hassab; Mohamed A. Al-Banoby; et al. (Livestock Science, 2026)

Adsorption Performance and Life Cycle Assessment of Raw and Chemically Modified Coconut Shell Biochar for Methylene Blue Removal - Gokulan Ravindiran; Yamala Midhun Sai; Datla Lakshmi Trishitha; Varshita Kamepalli; Kulchari Rohith; J. Saravanan; K. Karthick; P. V. S. Gopi Raghunadh; Wael S. Al-Rashed; Gasim Hayder (International Journal of Environmental Research, 2026)

Smart Innovations and Sustainability in EU Waste Material Trading: Evidence of Quantile Decomposition in EU Circular Economy Transitions - Eszter Lukács; Peter Németh; Md. Rashed; Mohammad Fakhrul Islam (Circular Economy and Sustainability, 2026)
Europe stands at the threshold of a transformative circular economy transition across the European Union (EU). However, to achieve a sustainable framework that improves resource use, transforms waste generator behavior, and guides high-polluting industries toward circular practices, the EU needs more efficient recovery networks and material circulation across member states. Using 14 years of cross-border waste recovery data from 2010 to 2023 across 27 EU countries, this study investigates the heterogeneous associations of several determinants of exports of notified waste for recovery (EWR) through the method of moments quantile regression (MMQR) to decompose location (median) and scale (dispersion) effects, alongside bootstrap quantile regression (BSQR) for robustness, the generalized method of moments (GMM) for persistence and endogeneity, and Granger causality tests for directional relationships. Our investigation identifies several policy factors associated with transboundary recovery participation and circular economy transition. The relationship also shows reverse Granger causality. AI innovation shows no significant associations with waste trade or the possibility of deployment gaps, but R&D intensity shows robust positive associations across all quantiles, with forward Granger causality supporting causal precedence. The recycling rate of municipal waste (RMW) has monotonically increasing associations in all quantiles and has bidirectional Granger causality, implying possible feedback mechanisms. These findings, put together, inform policymakers to consider market mechanisms, institutionalizing R&D investment, emphasizing infrastructure development, driving economic growth, and leveraging technological capabilities to support sustainable transboundary waste recovery networks and circular transition across the EU.

Electricity poverty in sub-Saharan Africa: Do green electricity generation and human development influence sustainable energy foreign direct investment in the long and short run? - Ahmed R. Rashed (The Social Science Journal, 2026)

Migration and migratory connectivity of Greater Spotted Eagles (Clanga clanga) wintering at the head of the Arabian Gulf - Michael J. McGrady; Omar Al Sayed Omar; Rashed Al Hajji; Matthias Schmidt; Madan K. Oli (Journal of Ornithology, 2026)

Effectiveness of PRF alone versus PRF plus biphasic calcium phosphate as a scaffold for gingival mesenchymal stem cells in induced vertical alveolar ridge defects - Aya Hussien; Ashraf M. Abu-Seida; Hala Abuel-Ela; Laila Rashed; Khaled Abdel-Ghaffar (Cell and Tissue Banking, 2026)

Morphogenesis of perithecia and rosette-like ascospores in Sordaria sclerogenia reveals virulence-associated metabolites and ultrastructural mechanisms of root invasion in lemon - Safaa A.M. Yousef; Motrih Al-Mutiry; Wael F. Shehata; Enas A. Almanzalawi; Tahani M. Alqahtani; Samiyah S. Al-Zahrani; Sarah Al-Rashed; Yasser S. Mostafa; Saad A. Alamri; Mohamed A. Abou-Zeid (Physiological and Molecular Plant Pathology, 2026)

Blended median-trimmed mean filter for random noise suppression in GPR data - Wentian Wang; Mohamed Rashed (Journal of Applied Geophysics, 2026)

Canagliflozin attenuates Parkinson’s disease and is associated with modulation of gut-inflammasome–brain axis in rats - Nada K. Gamal; Rafik Fakhry; Youmna Hatem; Engy Rashed; Reem Marzouk; Ahmed K. M. Bukr; Kerolos Safwat; Mohamed Mamdouh; Ahmed AbdElFatah; Abdelrahman Atallah; Heba Attia; Iriny M. Ayoub; et al. (Inflammopharmacology, 2026)
Recent evidence links gut dysbiosis and the gut-brain axis to the pathophysiology of Parkinson’s disease (PD), which is considered one of the most common neurodegenerative illnesses and is characterized by motor symptoms and a gradual loss of nigral dopaminergic neurons. Canagliflozin (CANA), a sodium–glucose cotransporter-2 inhibitor with emerging anti-inflammatory and antioxidant properties, has recently gained attention for its neuroprotective effects beyond glycemic control. This research aimed to examine the neuroprotective potential of CANA in a rat model of PD, focusing on its potential effect on the gut-inflammasome–brain axis. Rats were treated with rotenone (ROT) (2 mg/kg, subcutaneous) and/or CANA (20 mg/kg, oral) for 30 consecutive days. Behavioral assessment ( n = 13), biochemical assays ( n = 6), and histological and immunohistochemical analysis ( n = 3) were performed. Microbiome profiling ( n = 3) using 16S rRNA amplicon sequencing was conducted using three pooled fecal samples/group, with each pool prepared from fecal material collected from three rats and fecal metabolomic profiling ( n = 5) was performed to assess microbial metabolites. ROT intoxication caused significant motor impairments, including decreased locomotor activity, poor coordination, and increased catalepsy. Further histological examination demonstrated dopaminergic neuronal loss and α-synuclein aggregation in the substantia nigra and striatum. CANA treatment enhanced motor function, conserved neuronal integrity, and decreased α-synuclein accumulation. Moreover, ROT altered the gut microbiota with selective taxonomic shifts, including enriched abundance of Parabacteroides and Ruminococcaceae with depleted Prevotella -related taxa, in addition to fecal metabolite profile alteration. Consequently, it increased colonic oxidative stress and weakened tight junctions, all of which enhanced LPS translocation. This systemic endotoxemia generated oxidative stress, dyslipidemia, and NF-κB/NLRP3 inflammasome activation. Conversely, CANA restored gut microbial balance and their metabolites, and gut integrity, decreased LPS leakage, and reduced systemic and central oxidative stress and inflammation, preventing inflammasome activation and α-synuclein aggregation. Collectively, these findings suggest that CANA may exert neuroprotective effects in ROT-induced PD associated with modulating the gut-inflammasome–brain axis.

Deciphering the Genetic Mechanisms Driving Carbapenem Resistance: A Multicenter Study from Seven Egyptian Governorates Using Multiplex PCR and Whole Genome Sequencing - Maha Gad; May Sherif; Sara Essam; Doaa Gamal; Inas El-Defrawy; Mohammed Abdelhakeem; Omnia Taher; Radwa Abdel-Latif; Ahmed Shoala; Sherine Shawky; Hebatallah Rashed; Hamida Gohar; et al. (Current Microbiology, 2026)

Evaluating the hepatotoxicity and nephrotoxicity of herbal medicine on swiss albino mice: an in-vivo, in-vitro and in-silico insights - Md. Murshid Alom; Md. Rausan Zamir; Nazmul Islam; Md. Khalekuzzaman; Rashed Zaman; Md. Asadul Islam (In Silico Pharmacology, 2026)

Distinct impact of splenic denervation and the role of TRPV1 in LIPUS-induced anti-inflammatory milieu in the kidney: Involvement of neurochemicals, Nrf2/HO-1 modulation and change of macrophage phenotype - Omaima Mohammed Abdelwahed; Basma Emad Aboulhoda; Sarah Ali Abdelhameed Gouda; Tarek Shoukry; Laila Rashed; Marwa Alkaffas; Ebtehal Gamal Abdelhady; Mansour A. Alghamdi; Hend Abdalla; Nivin Sharawy (Tissue and Cell, 2026)

Fabrication and characterization of polylactide/polyethylene glycol/Chlorella vulgaris biocomposite films - Jasim Ahmed; Tahani A. Al-Shamary; Rashed A. Al-Zufairi; Salah Al-Enezi; Vinod Kumar (Food Packaging and Shelf Life, 2026)

Coupled heat and moisture transfer modeling of a PCM–desiccant wall panel for indoor temperature and humidity control: A one-dimensional hygrothermal approach - Abdulwahab A. Alnaqi; Jalal Alsarraf; Abdullah A.A.A. Al-Rashed (Energy and Buildings, 2026)

Tropical climate drivers (ENSO, IOD, and MJO) and seasonal flood variability in Bangladesh - Md Rashed Chowdhury; Adiba Mosharraf; Md. Ashraful Islam; Shamoeta Zaman; Md. Abdulla Hel Kafi; Md. Sohel Masud; SM Mahbubur Rahman (Theoretical and Applied Climatology, 2026)

Otolith weight as a predictor of age in Sillaginopsis panijus (Hamilton, 1822): Development of a preliminary age estimation model - Mohammad Rashed; KM Jakaria Shuvo; Siam Sheikh Sadi; Md Abdul Baten (Estuarine, Coastal and Shelf Science, 2026)

Construction of carbon-modified TiO2 nanocomposite with various surfactants for photocatalytic degradation of benzene, toluene, ethylbenzene, and xylene under visible light - Adel Al-Haddad; Adel A. Ismail; L.A. Al-Hajji; Rashed Alyaseen; S.A. Ahmed; Mariam Alsaidi; Vinod Kumar Nair; Abrar Alrashed; Metwally Madkour (Journal of Water Process Engineering, 2026)

Corrigendum to “Numerical investigation of flare gas combustion in ethylene cracking furnaces”. [Fuel 381 (2025) 133381] - Rashed Al-ajmi; Mohammed Al-Shaghdari; Abdellatif M. Sadeq; Samer F. Ahmed; Abdulrahman S. Almutari (Fuel, 2026)

Comparative modeling of laboratory-scale biological and real industrial desulfurization processes using artificial neural networks and response surface methodology: Toward clean fuels and sustainable bioenergy - Saja Mohsen Alardhi; Sura Jasem Mohammed Breig; Ali Dawood Salman; Israa Abass Rashed; Mustafa Adnan; Fadhil Ayoob Kareem; Malik M. Mohammed (Biomass and Bioenergy, 2026)

Participatory Co-Design for Human–Elephant Coexistence: Integrating Local Knowledge into Early Warning System Planning in Odisha - Balu M. Menon; Tarek Rashed; Lekshmi Venkitesh P; Vasundharan Nidhi; Rao R. Bhavani (Environmental Management, 2026)

Geo-spatial assessment of human-induced soil erosion and environmental hazard using the RUSLE model: A path toward sustainable land management in the Duhok Watershed - Gaylan Rasul Faqe Ibrahim; Kamaran Wali Mahmood; Srusht Othman Rashed (Journal of Mountain Science, 2026)

Comparative thermo-environ-economic analysis of solar-assisted and conventional ejector-compression heat pump systems for space heating - Jalal Alsarraf; Abdulwahab A. Alnaqi; Abdullah A.A.A. Al-Rashed (Energy and Buildings, 2026)

Habitat suitability analysis for sea cucumber mariculture development in the coastal waters of Bangladesh - Muhammad Mizanur Rahman; Subrata Sarker; Md. Rashed Talukder; Md. Shahadat Hossain; Md. Al Mamun; Tanjida Sultana (International Journal of Remote Sensing, 2026)

How can Mentha piperita oil affect Trichinella spiralis adults and larvae? In vitro and in vivo studies - Maha Mohamed Gomaa; Inass Ibrahim Ahmed Zaki; Hoda Adel Rashed (Veterinary Parasitology, 2026)

A novel synchronous spectrofluorimetric analysis of naproxen and hydroxychloroquine in plasma and pharmaceuticals at nanogram levels: Comparative greenness and sustainability assessment - Zeinab Adel Nasr; Noha Salem Rashed; Eman Abdalla Shalaby; Galal Magdy (Sustainable Chemistry and Pharmacy, 2026)

The feasibility of calculating the enrichment of 235U using the PIGE method with high-energy protons - Marzieh Hassanpour; Mehdi Hassanpour; MohammadReza Rezaie; Mohammad Rashed Iqbal Faruque (Annals of Nuclear Energy, 2026)

Does regularity quality enhance sustainability performance? International evidence - Mousumi Zaman; Rasol Eskandari; Rashed Khan (Journal of Environmental Management, 2026)

Solar-responsive biopolymer–carbon nanotubes aerogel for efficient atmospheric water harvesting - Amira S. Mohammed Ali; Ahmed O. Rashed; Faisal Almarzooqi; Maguy Abi Jaoude; Fawzi Banat (Chemical Engineering Journal, 2026)

A review on gut microbiota and migraine severity: a complex relationship - Noha M. Gamil; Rana M. Ghorab; Reham Z. Elsadawy; Nada M. Khadrawy; Mohamed Abdelhamid; Khalid A. Ismael; Omar A. Mohamed; Mohamed M. Ata; Habiba T. Jalal; Joumana E. Zeidan; Reem T. Rashed; Riham A. El-Shiekh (Inflammopharmacology, 2026)
The gut-brain axis plays a vital role in migraine pathophysiology. Studies highlight reciprocal interactions between the central nervous system and the gastrointestinal tract. Previous research suggests that factors such as gut microbiota profiles, inflammatory mediators, neuropeptides, serotonin pathways, stress hormones, and nutritional substances influence this interaction. The pathophysiology of migraine has been linked to changes in the gut-brain axis, which affects migraine severity and frequency. Additionally, dietary approaches, including the ketogenic diet, vitamin D supplementation, omega-3 intake, probiotics, and weight loss plans, have shown promising effects in reducing migraine symptoms by positively impacting the gut microbiota and the gut-brain axis. Understanding these connections could lead to novel therapeutic strategies for effectively managing migraines. It is worth noting that research highlights several innovative treatments for migraine, such as Zelirex and Cevimide, implantable devices like Cefaly and Revilion, and new effective routes of administration for Sumatriptan. Finally, patients’ perspectives and concerns were thoroughly discussed, with a focus on future directions in the migraine-gut axis research.

Integrating Health in the Water-Energy-Food Nexus: A Comprehensive Review of Interdependencies, Challenges, and Future Research Opportunities - Rashed Albatayneh; Rabi Mohtar; Zainab Ashkanani; Bassel Daher; Wael K. Al-Delaimy (Current Environmental Health Reports, 2025)
Purpose of Review The Water-Energy-Food (WEF) Nexus has become a crucial framework for understanding resource interdependencies, nevertheless its integration with health remains underexplored. This review paper examines the current literature in the Water Energy Food Health (WEFH) Nexus, emphasizing the complex relationships between resource security and public health outcomes. Through a systematic literature review, the existing research trends, methodological approaches, and regional disparities in WEFH studies are analyzed. Recent Findings While health is an inherent component of resource systems, it is often treated as an externality rather than a central determinant. The review revealed that out of 1175 research articles screened, only 21 discussed WEFH as an integrated nexus. Hence, there is a crucial need for a comprehensive Water, Energy, Food, and Health research. Summary The paper proposes a conceptual WEFH integration that positions health as both an outcome and a driver of sustainable resource management based on epidemiological evidence. By analyzing health metrics implicit to the WEF nexus, the study provides insights for researchers and policymakers seeking to develop holistic strategies for resilience and equity in resource governance.

Arabic gum, Multi-industrial usage materials - Soran Abdrahman Ahmad; Serwan Khwrshid Rafiq; Hersh F Mahmood; Rukhosh Jawhar Rashed; Sherzad Mohammed Ali; Hezha Nasr Hussein (Next Research, 2025)

Retraction notice to “Visible-light-driven photodegradation of organic pollutants by simply exfoliated kaolinite nanolayers with enhanced activity and recyclability” [Environ. Res. Volume 214, Part 3, November 2022, 113960] - Sabrin M. Abdo; Soliman I. El-Hout; Ahmed Shawky; Mohamed Nageeb Rashed; Said M. El-Sheikh (Environmental Research, 2025)

The role of visfatin and omentin-1 gene polymorphism in pancreatic ductal adenocarcinoma (PDAC) - Eman AE Badr; Waheed M. Salem; Yostena Mekhail; Hager Mohamed Rashed (Molecular Biology Reports, 2025)

The possible role of hsa_circ_0049356 and hsa-miR-338-3p in systemic lupus erythematosus disease - Mai Samir; Rana Mohamed Abd el-rahman; Laila Rashed; Mohamed Magdy; Doaa M. Gharib (Molecular Biology Reports, 2025)

Molecular docking and differential rbcl gene expression reveal variation in glyphosate herbicide tolerance of sugarcane varieties - Kawthr S. M. Allam; M. Magdy; A. M. Abd El-Aal; Nasr S. Khalil; M. A. Rashed; A. H. Atta; Reham I. AbdelHamid (Molecular Biology Reports, 2025)

Interruption of the Gut Integrity Contributes to Early Accumulation of Amyloid-β in the Enteric Nervous System in Rats Supplemented with a High-Fat Diet - Zeinab Gawish; Maha Gamal; Dalia Azmy Elberry; Esraa A. Hegazy; Laila Ahmed Rashed; Sara Adel Hosny; Marwa Nagi Mehesen; Asmaa Mohammed ShamsEldeen (Molecular Neurobiology, 2025)
Consumption of a high-fat diet (HFD) contributes to numerous chronic illnesses, including neurological disorders and gastrointestinal dysfunction. The study design included four groups, each consisting of six rats: the control group was fed regular chow, while groups 2 (HFD 2W), 3 (HFD 4W), and 4 (HFD 8W) were given a 60% HFD for 2, 4, and 8 weeks, respectively. A significant change in the latency to the platform in the water maze, a decrease in the percentage of successful cycles in the Y-maze, and a reduction in the percentage of time spent with the novel object were observed between the baseline and endpoint results in the HFD 4W and HFD 8W groups; notably, this was not the case in the control and HFD 2W groups. Consistent with the increased duration of HFD intake, marked damage to the cortical pyramidal cells as well as the mucosa of the ileum and colon was recorded. The optical density of amyloid deposition was significantly increased in the myenteric plexus before the cerebral cortex. In conclusion, increasing the duration of 60% HFD consumption was associated with significant deterioration of spatial and working memory, an increase in lipid profile, and amyloid deposition in the enteric nervous system, which began even before the observable involvement of the cerebral cortex. Graphical Abstract

Platelet-rich plasma mitigates lipopolysaccharide-driven acute lung injury by targeting the cGAS-induced STING/ERS/TBK1/IRF3/NF-κB pathway in male rats - Fatma E. Hassan; Neamat Mahmoud Abd Elgilil; Basma Emad Aboulhoda; Hend Ahmed Abdallah; Laila A. Rashed; Shimaa Magdy Shaban (Histochemistry and Cell Biology, 2025)

ENSO and seasonal climate variability in the Maldives: an analysis of early warning opportunities - Md Rashed Chowdhury; Azeema Ahmed; Sheena Moosa; Shazla Mohamed (Theoretical and Applied Climatology, 2025)

Combined Effects of Parasitic Infection and Heavy Metal Exposure on Health and Profitability of Cultured African Catfish (Clarias gariepinus) - Mahmoud Radwan; Mohammad R. K. Abdel-Samad; Aya Ramadan Rashed; Wafa Mohammed Al-Otaibi; Shahd Yassir; Moussa Attia Moussa (Biological Trace Element Research, 2025)

Nutrient Analysis of Raw and Sensory Evaluation of Cooked Red Tilapia Fillets (Oreochromis sp.): A Comparison Between Aquaculture (Red Kenyir™) and Wild Conditions - Aswir Abd Rashed; Nurliayana Ibrahim; Nurul Izzah Ahmad; Mariam Marip; Mohd Fairulnizal Md Noh; Mohammad Adi Mohammad Fadzil (Fishes, 2025)
The tilapia sector is advancing due to breakthroughs in aquaculture techniques and genetic enhancements. Comprehending sensory qualities is crucial for producers striving to meet market demands efficiently. As consumer preferences play a significant role in shaping the market, enhancing the sensory attributes of both farmed and wild red tilapia will be key to ensuring their success in the competitive aquaculture industry. One of Malaysia’s most prominent aquaculture projects is the Como River Aquaculture Project located in Kenyir Lake, where tilapia fish farming, trademarked as Red Kenyir™, is conducted. Thus, this study aimed to evaluate the nutrient analysis of raw and five sensory attributes (appearance, texture, smell, taste, overall quality) of filets from Red Kenyir™ and wild red tilapia (Oreochromis sp.). Red Kenyir™ were fed three different commercial diets (A, B, and C) from fingerling to adulthood, while wild tilapia (W) was sourced from the market. Proximate and nutritional analyses were conducted based on the standard food analysis protocol by AOAC/AOCS. To the best of our knowledge, this is the first study to comprehensively document the nutrient analysis of raw and consumer sensory perception of cooked Red Kenyir™ aquaculture tilapia in direct comparison with wild red tilapia. The sensory evaluation was conducted using a consumer preference test. Statistical analysis was performed using SPSS. Nutrient analysis showed that Red Kenyir™ tilapia had lower fat (0.25–1.37 g/100 g vs. 4.30 g/100 g) and lower energy (77.38–113.46 kcal/100 g vs. 132.79 kcal/100 g) levels. Protein levels varied across groups (19–26.54 g/100 g vs. 22.95 g/100 g). The tryptophan content of the Red Kenyir™ tilapia samples ranged between 0.13 and 0.23 g/100 g, while the wild tilapia contained 0.19 mg/100 g. Sensory evaluation with 36 panelists revealed no significant differences in appearance, texture, or smell (p > 0.05). However, wild tilapia scored slightly higher in taste (4.14) than Red Kenyir™ (3.54–3.71) for steamed preparation (p

Design and development of industrial prototype of spot specific orchard sprayer using ultrasonic sensing system and advanced pressure control mechanism - Arshed Ahmed; Shoaib Rashid Saleem; Muhammad Naveed Tahir; Shahram Hamza Manzoor; Qamar Zaman; Zhao Zhang; Rashed Ahmed (Computers and Electronics in Agriculture, 2025)

Correction: The potential liver injury induced by metronidazole-provoked disturbance of gut microbiota: modulatory effect of turmeric supplementation - Abdulaziz Q. Ali; Deema Kamal Sabir; Amal F. Dawood; Mohammed Abu-Rashed; Abdulrahman Hasari; Faiz Gharqan; Salem Alnefaie; Lama E. Mohiddin; Maya M. Tatry; Dana A. Albadan; Mohanad M. Alyami; Mohammed F. Almutairi; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Geometric optimization of a turbulator in nanofluid flow around a bundle of nuclear reactor fuel rods using the response surface methodology - Jalal Alsarraf; Abdulwahab A. Alnaqi; Abdullah A.A.A. Al-Rashed (Annals of Nuclear Energy, 2025)

Navigating the nuclear tide: A comprehensive review of challenges, opportunities, and advances in managing marine contamination by radioactive contaminants - Adewale Giwa; Jamiu O. Eniola; Ayesha Bilal Salem; Aysha Ali Alshamsi; Kinda Amin Omar; Noor Saleh Alnuaimi; Sara Ghazwan Al-Fahad; Lulwa Ammar Rashed (Marine Pollution Bulletin, 2025)

Life cycle assessment of scaled-up pyrite-based solid-state batteries for energy storage applications - Md Rashed Hossain; Muyue Han; Lin Li (Journal of Cleaner Production, 2025)

The Effects of a Novel Supplement Containing Probiotics and Vitamin D as an Adjutant Therapy on sNFL and Th Cell Profiles in Patients with Multiple Sclerosis: A Randomized, Double-Blind, Placebo-Controlled Trial - Alireza Zali; Saba Sadeghi Rashed; Seyedeh Nikan Nejat; Nahid Beladi Moghadam; Javad Arasteh; Saba Taheri; Mehri Salari; Amir M Mortazavian; Mehran Ghaffari; Maryam Tajabadi Ebrahimi (Journal of Pharmaceutical Innovation, 2025)

Evaluating water supply and demand growth in the Gulf Cooperation Council countries: projections and policy implications for sustainable water resources management - Amjad Aliewi; Muhammad Al Rashed; Dalal Sadeqi; Harish Bhandary; Ahmed Sefelnasr; Mohsen Sherif; Ahmed Murad; Dalal Alshamsi; Abdel Azim Ebraheem (Arabian Journal of Geosciences, 2025)

Zonisamide nanodiamonds for brain targeting: A comprehensive study utilising in silico, in vitro, in vivo, and molecular investigation for successful nose-to-brain delivery for epilepsy management - Nihal Mohamed Elmahdy Elsayyad; Omar A. Elkady; Mohamed M. Swidan; Hassan M. Rashed; Tamer M. Sakr; Amr M. Abdelhamid; Mai A. Zaafan; Hanan M. El-Laithy (Drug Delivery and Translational Research, 2025)
The blood–brain barrier (BBB) is a stringent barrier that restricts the successful brain delivery of polar neurotherapeutics molecules. One such molecule is Zonisamide (ZNS), a hydrophilic centrally acting anti-epileptic drug. This study aims to overcome the poor ZNS BBB permeability using the nose-to-brain (NTB) carbon-based biocompatible nanodiamonds (ND) delivery system to deliver ZNS directly to the brain, bypassing the BBB, thereby enhancing its efficacy and reducing systemic side effects associated with oral ZNS currently available formulation in clinical practice. Intranasal (IN) ND-ZNS formulations were optimised using an Artificial neuronal network (ANN) and assessed for particle size (PS), zeta potential, loading efficiency (%LE), morphology, and in vitro release. The optimum radiolabelled ND-ZNS complex F1 biodistribution in different organs and its pharmacokinetics were compared to oral and IN-free ZNS in mice. Temporal lobe epilepsy (TLE) model in rats was used to compare the anti-epileptic activity of IN ND-ZNS F1 to IN free ZNS by assessing brain activity, epileptic biomarkers such as (brain neuronal specific enolase (NSE), neurofilament light polypeptide (NEFL), and matrix metallopeptidase-9 (MMP-9)), hippocampal histopathology and the modulatory effect on epigenetic miR-199/SIRT-1 and PVT-1/BDNF pathways. Optimized ND-ZNS complex F1 consists of a ZNS:ND ratio of 1:2 and sonicated for 5 min exhibited the least PS (193.7 ± 19.3 nm), adequate %LE (87.1 ± 9.2%) similar to ANN predictions, with a biphasic in vitro release profile of ZNS, beneficial for both acute and chronic epilepsy treatment. The IN delivery of ND-ZNS complex F1 showed preferential higher in vivo brain uptake with minimal systemic exposure linked with higher brain/blood ratio and significant ( p ≤ 0.05) overall enhanced pharmacokinetics expressed by C max and AUC (0-120min) when compared to oral and IN free ZNS . Moreover, the TLE model confirmed the improved anti-epileptic activity of F1 compared to IN-free ZNS regarding brain activity and hippocampal histopathology, significant suppression of serum NSE, NEFL, MMP-9 levels, miR-199/SIRT-1 pathway, and normalization of PVT-1/BDNF pathway. Therefore, ND used in this study could be a novel, promising carrier to target ZNS directly to the brain via the IN route for effective epilepsy management with less drug dosing and the least systemic side effects. Graphical Abstract

Study on the influence of pile arrays on near-trapped modes based on generalized finite difference method - Lanlan Li; Zhuojia Fu; Juraj Mužík; Youssef F. Rashed; Yan Gu (Ocean Engineering, 2025)

Association between objectively assessed physical activity and kidney function among female agricultural workers in hot environments in Spain - Sarah Koch; Joren Buekers; Ana Espinosa; Juan Gómez-Salgado; Gabriel Pombo; Loes Werkman; Lourdes Arjona; Ali Al Rashed; Ben Caplin; Manolis Kogevinas; Francisco Brocal-Fernandez; Amin Oomatia; et al. (Environmental Research, 2025)

Sensitivity analysis of parameters and optimization of produced entropy in a nuclear reactor with equilateral fuel rod arrangement and variable angle turbulators - Abdullah A.A.A. Al-Rashed; Abdulwahab A. Alnaqi; Jalal Alsarraf (Annals of Nuclear Energy, 2025)

Neuroprotective Effects of Alpha-Lipoic Acid Against Behavioral Toxicity, Oxidative and Inflammatory Damage Caused by Titanium Dioxide Nanoparticles - Mahmoud A. Khedr; Sara E. El-Kazaz; Rashed R. Rashed; Hossam G. Tohamy; Mustafa Shukry; Amira A. Goma (Biological Trace Element Research, 2025)
Titanium dioxide nanoparticles (TiO₂-NPs) are used widely in various industries, but emerging evidence suggests their ability to elicit neurotoxicity. The present study evaluated the alpha-lipoic acid (ALA) neuroprotective potential against TiO₂-NP-induced cognitive and molecular impairments in male Sprague–Dawley rats. Twenty-four rats were allocated into four groups: negative control, TiO₂-NPs (150 mg/kg, i.p.), ALA (50 mg/kg, orally), and TiO₂-NPs + ALA. Treatments were administered on alternate days for 28 days. Neurobehavioral tests, including the open field test (OFT), elevated plus maze (EPM), novel object recognition test (NORT), and Morris water maze (MWM), revealed that TiO₂-NPs impaired memory and increased anxiety-like behavior, while ALA co-treatment significantly restored behavioral performance. TiO₂-NPs exposure significantly decreased antioxidant enzymes (SOD, CAT, GSH), increased lipid peroxidation (MDA), elevated proinflammatory cytokines (TNF-α, IL-6), and apoptotic marker (caspase-3), and reduced neurotransmitter levels (GABA and dopamine). ALA administration reversed these alterations, indicating antioxidant, anti-inflammatory, and neuroprotective effects. Gene expression analysis showed TiO₂-NPs upregulated BAX, NF-κB, APP, and MAPT and downregulated BCL-2 and Nrf2, consistent with neurodegenerative and apoptotic signaling. ALA co-treatment normalized these gene expressions. Histopathological analysis confirmed structural damage in the cerebrum and cerebellum after TiO₂-NPs exposure, which ALA markedly improved. These findings suggest that ALA offers significant neuroprotection against TiO₂-NP-induced toxicity via its antioxidant, anti-inflammation, and anti-apoptosis properties, and supports being a potential protective agent against nanoparticle-induced neurodegeneration.

Discovering the inherent properties of CdS/TiTe2/Cu2Te near infrared photodetector: A computational analysis - Md. Rashed Miah; Md. Islahur Rahman Ebon; Ahnaf Tahmid Abir; Jaker Hossain (Next Research, 2025)

Metabolite Profiling of Alectryon Tomentosus Leaf Extract via GC/MS Analysis and Its Renal Protective Effect - Salma A. El Sawi; Elsayed A. Aboutabl; Khaled N. Rashed; Amany A. Sleem; Nermin A. Ragab (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2025)

Numerical analysis of combustion characteristics and emissions of recycled flare gas in ethylene cracking furnaces - TurkiM. AL-Amoodi; Rashed Al-ajmi; Abdellatif M. Sadeq; Mohammed Al-Shaghdari; Samer F. Ahmed (Journal of Cleaner Production, 2025)

Plastic waste for frost mitigation: A bio-inspired approach to enhance soil resilience and carbon sequestration - Farideh Pahlavan; Rashed Rahman; Mohammadjavad Kazemi; Tejo V. Bheemasetti; Elham H. Fini (Resources, Conservation and Recycling, 2025)

Environmental sustainability practices in SMEs: Insights from integrated PLS-SEM and fsQCA approaches - Mohammad Imtiaz Hossain; Yasmin Jamadar; Mohammad Fakhrul Islam; Md. Rashed; Tania Akter (Journal of Cleaner Production, 2025)

Numerical investigation of the potential of using hydrogen as an alternative fuel in an industrial burner - Rashed Al-ajmi; Abdulhafiz H. Qazak; Abdellatif M. Sadeq; Mohammed Al-Shaghdari; Samer F. Ahmed; Ahmad K. Sleiti (Fuel, 2025)

Fatigue Reliability Analysis of Offshore Wind Turbines Under Combined Wind–Wave Excitation via Direct Probability Integral Method - Jingyi Ding; Hanshu Chen; Xiaoting Liu; Youssef F. Rashed; Zhuojia Fu (Journal of Marine Science and Engineering, 2025)
As offshore wind turbines develop into deepwater operations, accurately quantifying the impact of stochastic excitation in complex sea environments on offshore wind turbines and conducting structural fatigue reliability analysis has become challenging. In this paper, based on long-term wind–wave reanalysis data from the South China Sea, a novel direct probability integral method (DPIM) is developed for the stochastic response and fatigue reliability analysis of the key components for the floating offshore wind turbine structures, under combined wind–wave excitation. A 5 MW floating offshore wind turbine is considered as the research object, and a comprehensive analysis of the wind turbine system is performed to assess the short-term fatigue damage at the tower base and blade root. The proposed method’s accuracy and efficiency are validated by comparing the results to those obtained from Monte Carlo simulations (MCS) and a subset simulation (SSM). Additionally, a sensitivity analysis is conducted to evaluate the impact of different environmental parameters on fatigue damage, providing valuable insights for the design and operation of FOWTs in varying sea conditions. Furthermore, the results indicate that the fatigue life of floating offshore wind turbine (FOWT) structures under combined wind–wave excitation meets the design requirements. Notably, the fatigue reliability of the wind turbine under aligned wind–wave conditions is lower compared to misaligned wind–wave conditions.

Integrating machine learning for precision agriculture waste estimation and sustainability enhancement - Abderrahim Lakhouit; Wael S. AL Rashed; Sumaya Y.H. Abbas; Mahmoud Shaban (Computers and Electronics in Agriculture, 2025)

Linking the blue economy to Women's empowerment to create avenues for the realization of ocean sustainability targets in the global south - Baker Matovu; Raimund Bleischwitz; Isaac Lukambagire; Linda A. Etta; Meltem Alkoyak-Yildiz; Rashed Tarek; Ming-An Lee; Mubarak Mammel; S. Anusree; Ammu S. Suresh (Ocean & Coastal Management, 2025)

Optimizing encapsulation of garlic and cinnamon essential oils in silver nanoparticles for enhanced antifungal activity against Botrytis cinerea pathogenic disease - Nahla Alsayd Bouqellah; Awatif M. Abdulmajeed; Fawiziah Khalaf Rashed Alharbi; Ehab Mattar; Faisal Al-Sarraj; Ahmed M. Abdulfattah; Mohamed M. Hassan; Alaa Baazeem; Helal F. Al-Harthi; Arafa Musa; Tahani A.Y. Asseri; Mona H. Soliman (Physiological and Molecular Plant Pathology, 2025)

Genome-wide analysis of TCP family genes and their constitutive expression pattern analysis in the melon (Cucumis melo) - Md Jahid Hasan Jone; Md Nure Adil Siddique; Manosh Kumar Biswas; Mohammad Rashed Hossain (Genes & Genomics, 2025)

Structural based joint inversion of magnetometry and DC resistivity data through cross gradient constraint - Ali Dehghan Mongabadi; Ahmad Zarean Shirvanehdeh; Aynur Nasseri; Rashed Pourmirzaee (Acta Geodaetica et Geophysica, 2025)

Numerical investigation of flare gas combustion in ethylene cracking furnaces - Rashed Al-ajmi; Mohammed Al-Shaghdari; Abdellatif M. Sadeq; Samer F. Ahmed; Abdulrahman S. Almutari (Fuel, 2025)

Numerical investigation of the geometric parameters effect of helical blades installed on horizontal geo heat exchanger - Abdulwahab A. Alnaqi; Abdullah A.A.A. Al-Rashed; Jalal Alsarraf (Geothermics, 2025)

Novel Isoforms of Adhesion G Protein-Coupled Receptor B1 (ADGRB1/BAI1) Generated from an Alternative Promoter in Intron 17 - Rashed Rezwan Parag; Takahiro Yamamoto; Kiyotaka Saito; Dan Zhu; Liquan Yang; Erwin G. Van Meir (Molecular Neurobiology, 2025)
Brain-specific angiogenesis inhibitor 1 (BAI1) belongs to the adhesion G-protein-coupled receptors, which exhibit large multi-domain extracellular N termini that mediate cell–cell and cell–matrix interactions. To explore the existence of BAI1 isoforms, we queried genomic datasets for markers of active chromatin and new transcript variants in the ADGRB1 (adhesion G-protein-coupled receptor B1) gene. Two major types of mRNAs were identified in human/mouse brain, those with a start codon in exon 2 encoding a full-length protein of a predicted size of 173.5/173.3 kDa and shorter transcripts starting from alternative exons at the intron 17/exon 18 boundary with new or exon 19 start codons, predicting two shorter isoforms of 76.9/76.4 and 70.8/70.5 kDa, respectively. Immunoblots on wild-type and Adgrb1 exon 2 -deleted mice, reverse transcription PCR, and promoter-luciferase reporter assay confirmed that the shorter isoforms originate from an alternative promoter in intron 17. The shorter BAI1 isoforms lack most of the N terminus and are very close in structure to the truncated BAI1 isoform generated through GPS processing from the full-length receptor. The cleaved BAI1 isoform has a 19 amino acid extracellular stalk that may serve as a receptor agonist, while the alternative transcripts generate BAI1 isoforms with extracellular N termini of 5 or 60 amino acids. Further studies are warranted to compare the functions of these isoforms and examine the distinct roles they play in different tissues and cell types.

A machine learning-based approach for flash flood susceptibility mapping considering rainfall extremes in the northeast region of Bangladesh - Md Enayet Chowdhury; A.K.M. Saiful Islam; Rashed Uz Zzaman; Sharfaraj Khadem (Advances in Space Research, 2025)

Capacity of detergent to increase the efficacy of bio-pesticides and chemical pesticides against giant mealybug, Drosicha mangiferae (Homoptera: Pseudococcidae) - Mohammad Shaef Ullah; Md. Mehedi Hassan Sharif; Ayon Dey; Md. Mojammel Haque; Md Tafsir Nur Nabi Rashed (International Journal of Tropical Insect Science, 2024)

Unraveling the impact of greenhouse pepper resistance on biological performance of the broad mite Polyphagotarsonemus latus (Acari: Tarsonemidae) - Elnaz Fadaei; Mohammad Mehrabadi; Abdoolnabi Bagheri; Arash Rashed; Yaghoub Fathipour (Crop Protection, 2024)

A continuous flow microreactor as a practical tool for the synthesis of active pharmaceutical ingredients - K. Vijaya Bhaskar; Mohammad Rashed; K. Subrahmanya Bhat; Jechan Lee; Ki-Hyun Kim; Kezia Buruga (Process Safety and Environmental Protection, 2024)

Leveraging machine learning to model salinity and water flux for improved insights into forward osmosis membrane bioreactors - Ali Aldrees; Bilal Siddiq; Wael S. Al-Rashed; Muhammad Faisal Javed; Majid Khan (Journal of Water Process Engineering, 2024)

Examining the synergy of green supply chain practices, circular economy, and economic growth in mitigating carbon emissions: Evidence from EU countries - A.K.M. Mohsin; Markus Gerschberger; Michael Plasch; Sayed Farrukh Ahmed; Arifur Rahman; Md. Rashed (Journal of Environmental Management, 2024)

Seasonal fluctuations of heavy metal accumulation and gastrointestinal helminth induce oxidative stress and histological lesions in resident catfish Clarias gariepinus - Nadia A. El-Fahla; Marwa I. Saad El-Din; Yassmeen S.M. Abd El Mageed; Heba N. Gad EL-Hak; Nahla S. El-Shenawy; Hadeer Abd El-hak Rashed (Environmental Pollution, 2024)

Molecular mechanisms of extracellular-ATP-mediated colorectal cancer progression: Implication of purinergic receptors-mediated nucleocytoplasmic shuttling of HuR - Abdel-Aziz S. Shatat; Elsayed M. Mahgoup; Mohammed H. Rashed; Ibrahim G. Saleh; El-Sayed Akool (Purinergic Signalling, 2024)
One of the leading causes of cancer-related deaths worldwide is colorectal cancer (CRC). Extracellular ATP (e-ATP) and purinergic receptors (P2R) play a central role in CRC proliferation and progression. Human antigen R (HuR) is becoming more and more understood to be essential for the expression of genes linked to cancer. The current study demonstrates that ATP can mediate CRC (Caco-2 cells) progression via induction of HuR nucleocytoplasmic shuttling and subsequent expression of cancer-related genes, a consequence mostly mediated via the P2R receptor. It was also noted that suppression of HuR activity by using dihydrotanshinone I (DHTS) prevents cancer-related gene expression and subsequent CRC (Caco-2 cells) progression induced by ATP. The expression of cyclin A2/cyclin-dependent kinase 2 (CDK2), Bcl-2, ProT-α, hypoxia‐inducible factor1-α (HIF1-α), vascular endothelial growth factor A (VEGF-A), transforming growth factor-β (TGF-β) and matrix metallopeptidase 9 (MMP-9) induced by ATP were highly reduced in the presence of either PPADS (non-selective P2R antagonist) or DHTS. In addition, e-ATP-induced Caco-2 cell proliferation as well as cell survival were highly reduced in the presence of either PPADS or DHTS or selective CDK-2 inhibitor (Roscovitine) or selective Bcl-2 inhibitor (ABT-263). Furthermore, it was found that MMP-9 is critical for Caco-2 cells migration induced by e-ATP as demonstrated by a clear reduction in cells migration in the presence of a selective MMP-9 inhibitor (Marimastat). Collectively, these data demonstrate that ATP through P2R activation can induce HuR nucleocytoplasmic shuttling that could be translated into an increase in cancer-related genes expression and subsequent, cell proliferation and progression.

The potential liver injury induced by metronidazole-provoked disturbance of gut microbiota: modulatory effect of turmeric supplementation - Abdulaziz Qaid Ali; Deema Kamal Sabir; Amal F. Dawood; Mohammed Abu-Rashed; Abdulrahman Hasari; Faiz Gharqan; Salem Alnefaie; Lama E. Mohiddin; Maya M. Tatry; Dana A. Albadan; Mohanad M. Alyami; Mohammed F. Almutairi; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Provenance signature and tectonic setting of the Pliocene Tipam Sandstone Formation from the Chittagong Tripura Fold Belt of the Bengal Basin - Abu Sadat Md. Sayem; Papiya Mondal; Md. Sha Alam; Rashed Abdullah; Julleh Jalalur Rahman; Rumana Yeasmin (Journal of Sedimentary Environments, 2024)

Sensitivity analysis of cumulus parameterization scheme and data sources to simulate thunderstorms over Bangladesh using WRF model - M. Mozammel Hoque; Md. Salah Uddin Afsar; Mohammad Rashed Iqbal Faruque; S. Jamal Ahmed; A.T.M. Kaosar Jamil; M.A.K. Mallik; S.M. Quamrul Hassan (Advances in Space Research, 2024)

Assimilation of synthetic and real SWOT observations for the North Atlantic Ocean and Canadian east coast using the regional ice ocean prediction system - Guoqiang Liu; Gregory C. Smith; Audry-Anne Gauthier; Charlie Hébert-Pinard; Will Perrie; Maryam Rashed Al Shehhi (Frontiers in Marine Science, 2024)
The Surface Water Ocean Topography (SWOT) mission significantly improves on the capabilities of current nadir altimeters by enabling two-dimensional mapping. Assimilating this advanced data into high-resolution models poses challenges. To address this, Observing System Simulation Experiments (OSSEs) were conducted to evaluate the effects of both simulated and actual SWOT data on the Regional Ice Ocean Prediction System (RIOPS). This study examines the OSSEs’ design, focusing on the simulated observations and assimilation systems used. The validity of the OSSE designs is confirmed by ensuring the deviations between the assimilation system and the Nature Run (NR) align with discrepancies observed between actual oceanic data and OSSE simulations. The study measures the impact of assimilating SWOT and two nadir altimeters by calculating root mean square forecast error for sea surface height (SSH), temperature, and velocities, along with performing wave-number spectra and coherence analyses of SSH errors. The inclusion of SWOT data is found to reduce RMS SSH errors by 16% and RMS velocity errors by 6% in OSSEs. The SSH error spectrum shows that the most notable improvements are for scales associated with the largest errors in the range of 200-400 km, with a 33% reduction compared to traditional data assimilation. Additionally, spectral coherence analysis shows that the limit of constrained scales is reduced from 280 km for conventional observations to 195 km when SWOT is assimilated as well. This study also represents our first attempt at assimilating early-release SWOT data. A set of Observing System (data denial) experiments using early-release SWOT measurements shows similar (but smaller) responses to OSSE experiments in a two nadir-altimeter context. In a six-altimeter constellation setup, a positive impact of SWOT is also noted, but of significantly diminished amplitude. These findings robustly advocate for the integration of SWOT observations into RIOPS and similar ocean analysis and forecasting frameworks.

Enhancing the nutritional values of egg yolks of laying hens by different dietary sources of omega-3 fatty acids, vitamin e and trace elements - Youssef Attia; Ahmed A.Al Sagan; El-Sayed O.S. Hussein; Marai J. Olal; Tarek A. Ebeid; Abdulaziz A. Alabdullatif; Rashed A. Alhotan; Mohammed M. Qaid; Vincenzo Tufarelli; Gianluca Pugliese; Khaild A. Asiry; Sameer A. Nagadi; et al. (Livestock Science, 2024)

Demonstration scale treatment of drainage canal water in the Nile Delta through a combination of facultative lagoons and hybrid constructed wetlands - Dario Frascari; Ahmed Rashed; Elisa Girometti; Davide Pinelli; Attilio Toscano; Stevo Lavrnić (Journal of Environmental Management, 2024)

Which soil properties could affect the floristic composition of weed communities in saffron fields - Obaidullah Ghafory; Ghorban Ali Asadi; Mehdi Rastgoo; Mohammad Hassan Rashed Mohassel; Abdollah Mollafilabi (Biologia, 2024)

Effective vibrating barriers design for the Zoser pyramid using artificial neural network - Ahmed Fady Farid; Moataz A. Mabrouk; Youssef F. Rashed; Ashraf Ayoub (Soil Dynamics and Earthquake Engineering, 2024)

Amplification of avian influenza virus circulation along poultry marketing chains in Bangladesh: A controlled field experiment - Lisa Kohnle; Tridip Das; Md. Helal Uddin; Sanjib Chandra Nath; Md. Abu Shoieb Mohsin; Rashed Mahmud; Paritosh Kumar Biswas; Md. Ahasanul Hoque; Dirk Udo Pfeiffer; Guillaume Fournié (Preventive Veterinary Medicine, 2024)

Optimizing Mo2C-based catalytic system for efficient CO2 conversion and CO selectivity through carbon-nitrogen supporting and potassium promotion - Abdelrazek G. Galallah; Mohamed K. Albolkany; Ahmed E. Rashed; Wagih Sadik; Abdel-Ghaffar El-Demerdash; Ahmed Abd El-Moneim (Journal of Environmental Chemical Engineering, 2024)

Interleukin 1β receptor blocker (Anakinra) and regenerative stem cell therapy: two novel approaches effectively ameliorating diabetic cardiomyopathy - Lamiaa Mohamed Mahmoud; Aya Aly Ashraf Abdel Mageed; Jackline Moawad Saadallah; Mira Farouk Youssef; Liala Ahmed Rashed; Hania Ibrahim Ammar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Diabetic cardiomyopathy (DCM) is a serious common complication of diabetes. Unfortunately, there is no satisfied treatment for those patients and more studies are in critical need to cure them. Therefore, we aimed to carry out our current research to explore the role of two novel therapeutic approaches: one a biological drug aimed to block inflammatory signaling of the IL 1beta (IL1β) axis, namely, anakinra; the other is provision of anti-inflammatory regenerative stem cells. Wistar male rats were allocated into four groups: control group: type 2 diabetes mellitus (DM) induced by 6-week high-fat diet (HFD) followed by a single-dose streptozotocin (STZ) 35 mg/kg i.p., then rats were allocated into: DM: untreated; DM BM-MSCs: received a single dose of BM-MSCs (1 × 10 6 cell/rat) into rat tail vein; DM-Anak received Anak 0.5 μg/kg/day i.p. for 2 weeks. Both therapeutic approaches improved cardiac performance, fibrosis, and hypertrophy. In addition, blood glucose and insulin resistance decreased, while the antioxidant parameter, nuclear factor erythroid 2–related factor 2 (Nrf2) and interleukin 10 (IL10), and anti-inflammatory agent increased. Furthermore, there is a significant reduction in tumor necrosis factor alpha (TNFα), IL1β, caspase1, macrophage marker CD 11b, inducible nitric oxide synthase (iNOS), and T-cell marker CD 8. Both Anak and BM-MSCs effectively ameliorated inflammatory markers and cardiac performance as compared to non-treated diabetics. Improvement is mostly due to anti-inflammatory, antioxidant, anti-apoptotic properties, and regulation of TNFα/IL1β/caspase1 and Nrf2/IL10 pathways.

Cytoprotective effect of garlic alone versus co-administration of garlic and resveratrol in adriamycin-induced lung toxicity in albino rat: light microscopic, ultrastructural and immunohistochemical study - Noha A. Rashed; Omnia I. Ismail (Journal of Molecular Histology, 2024)

Examining the Influence of Zinc Oxide Nanoparticles and Bulk Zinc Oxide on Rat Brain Functions: a Comprehensive Neurobehavioral, Antioxidant, Gene Expression, and Histopathological Investigation - Amira A. Goma; Alyaa R. Salama; Hossam G. Tohamy; Rashed R. Rashed; Mustafa Shukry; Sara E. El-Kazaz (Biological Trace Element Research, 2024)
The study aimed to assess the impact of zinc oxide nanoparticles (ZnONPs) on rats’ neurobehavior compared to bulk zinc oxide (BZnO). Thirty male Sprague-Dawley rats were randomly assigned to five groups. The control group received Tween 80 (10%), while the ZnONP groups were given ZnONPs at 5 and 10 mg/kg body weight dosages, and the bulk zinc oxide (BZnO) groups received BZnO at the same dosages. Behavioral observations, neurobehavioral examinations, and assessments of brain tissue oxidative markers, neurotransmitter levels, and histopathological changes were performed. The results indicated that ZnONP at a dosage of 5 mg/kg improved general behavior, locomotor activity, memory, and recognition and reduced fearfulness in rats. Conversely, the higher dosage of 10 mg/kg and the bulk form had adverse effects on general behavior, locomotor activity, and learning ability, with the bulk form demonstrating the most severe impact—znONP-5 treatment increased antioxidant enzyme levels and decreased inflammatory markers. BZnO-5 exhibited lower oxidative stress markers, although still higher than BZnO-10. Furthermore, ZnONP-5 and BZnO-5 increased neurotransmitter levels compared to higher dosages. ZnONP-5 upregulated the expression of brain-derived neurotrophic factor (BDNF) mRNA, while BZnO-5 showed increased BDNF mRNA expression and decreased expression of genes related to apoptosis and inflammation. In summary, ZnONPs at 5 mg/kg demonstrated positive effects on rat brain function and behavior, while higher dosages and the bulk form had detrimental effects. In conclusion, the studies emphasized the importance of further assessing various doses and forms of zinc oxide on brain health, highlighting the significance of dosage considerations when using nanomaterials.

Optical Based Surface Plasmon Resonance Sensor for the Detection of the Various Kind of Cancerous Cell - Shah Ali Rafi; Wahiduzzaman Emon; Ahmed Afif Rafsan; Russel Reza Mahmud; Md. Faysal Nayan; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Ecological impacts and management strategies of pesticide pollution on aquatic life and human beings - Synan F. AbuQamar; Mohamed T. El-Saadony; Samar S. Alkafaas; Mohamed I. Elsalahaty; Sara S. Elkafas; Betty T. Mathew; Amal N. Aljasmi; Hajar S. Alhammadi; Heba M. Salem; Taia A. Abd El-Mageed; Rashed A. Zaghloul; Walid F.A. Mosa; et al. (Marine Pollution Bulletin, 2024)

Development and Enhancement of PCF-based Sensors for Terahertz-frequency Region Breast Cancer Cell Detection - A. H. M. Iftekharul Ferdous; Laxmi Rani; Md. Safiul Islam; Khalid Sifulla Noor; Sourav Roy; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Innovative Refractive Index Sensor Utilizing Terahertz Spectrum for Early Cancer Detection: a Photonic Crystal Fiber Approach - A. H. M. Iftekharul Ferdous; Md Naimur Rahman Naim; Khalid Sifulla Noor; Diponkar Kundu; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Geotechnical Evaluation of Consolidation and Conductivity of Synthetic Municipal Solid Waste - Rajeevkaran Paranthaman; Shahid Azam; Rashed H. Chowdhury (Geotechnical and Geological Engineering, 2024)

Publisher Correction: Heat Stress Modulates Superoxide and Hydrogen Peroxide Dismutation and Starch Synthesis during Tuber Development in Potato - Jobadatun Naher; Zahid Hasan Sabuj; Sahida Islam Sumona; Sheba Pada Chakraborty; Mohammad Rashed Hossain; Md. Motiar Rohman; Ujjal Kumar Nath (American Journal of Potato Research, 2024)

Heat Stress Modulates Superoxide and Hydrogen Peroxide Dismutation and Starch Synthesis during Tuber Development in Potato - Jobadatun Naher; Zahid Hasan Sabuj; Sahida Islam Sumona; Sheba Pada Chakraborty; Mohammad Rashed Hossain; Md. Motiar Rohman; Ujjal Kumar Nath (American Journal of Potato Research, 2024)

GC-MS analysis and pharmacological potentiality of Lasia spinosa (L.) Thwaites leaves and fruit extracts: an in vitro and in silico studies - Md. Anamul Haq; Md. Eram Hosen; Rakhi Rani; Alomgir Hossain; Mahmudur Rahman; Md Sagor Ali; Rashed Zaman; Md. Khalekuzzaman; Md. Asadul Islam; Amti Kumar Dutta; Uzzal Kumar Acharjee (In Silico Pharmacology, 2024)

Retraction Note: Amelioration of thioacetamide-induced hepatic encephalopathy in rats by low-dose gamma irradiation - Mona Abd El-Latif El-Ghazaly; Engy Refaat Rashed; Ghada Mahmoud Shafey; Hala Fahmy Zaki; Amina Salem Attia (Environmental Science and Pollution Research, 2024)

Risk-driven optimal scheduling of renewable-oriented energy hub under demand response program and energy storages: A novel Entropic value-at-risk modeling - Esmaeil Valipour; Ali Babapour-Azar; Ramin Nourollahi; Rashed Khanjani-Shiraz; Michael Römer (Sustainable Cities and Society, 2024)

Amelioration of cisplatin-induced neurodegenerative changes in rats and restoration of mitochondrial biogenesis by 6-bromoindirubin-3′-oxime: The implication of the GSK-3β/PGC1-α axis - Ola Magdy; Mohammed Eshra; Laila Rashed; Muhammed Maher; Sara Adel Hosny; Asmaa Mohammed ShamsEldeen (Tissue and Cell, 2024)

A study of cognitive computing in nanosatellite constellations for synergic autonomy in CisLunar space - Mohammed Irfan Rashed; Hyochoong Bang (Advances in Space Research, 2024)

Activated carbon and their nanocomposites derived from vegetable and fruit residues for water treatment - A.A. Thamer; A. Mustafa; H.Q. Bashar; Bao Van; Phuoc-Cuong Le; Miklós Jakab; T.R. Rashed; Karol Kułacz; MustafaM. Hathal; Viola Somogyi; D. Duc Nguyen (Journal of Environmental Management, 2024)

Engineering multifunctional UV-polymerizable imidazolidinyl urea-based methacrylate resin for 3D printing: Synthesis, characterization, and antimicrobial properties - Nagham Rashed; Krishanu Ghosal; Nadine Kana'an; Qi Wu; Konda Reddy Kunduru; Shady Farah (Chemical Engineering Journal, 2024)

Evaluation of skeletal muscle function in male rats with doxorubicin-induced myopathy following various exercise techniques: the significant role of glucose transporter 4 - Eman Osama; Effat Khowailed; L Rashed; A. Fawzy; Rokia Mohamad Hassan; Inas Harb; Muhammad Maher (Pflügers Archiv - European Journal of Physiology, 2024)
A common anthracycline antibiotic used to treat cancer patients is doxorubicin (DOX). One of the effects of DOX therapy is skeletal muscle fatigue. Our goal in this research was to study the beneficial effect of exercise on DOX-induced damaged muscle fibers and compare the effect of different exercise strategies (prophylactic, post- toxicity and combined) on DOX toxicity. Five groups were created from 40 male rats: group I, control group; group II, DOX was administered intraperitoneally for 2 weeks over 6 equal injections (each 2.5 mg/kg); group III, rats trained for 3 weeks before DOX; group IV, rats trained for 8 weeks after DOX; and group V, rats were trained for 3 weeks before DOX followed by 8 weeks after. Measures of oxidative damage (H 2 O 2 , catalase), inflammation (TNF-α), and glucose transporter 4 (GLUT4) expression on skeletal muscle were assessed. Also, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) was estimated. Skeletal performance was evaluated by contraction time (CT), half relaxation time (1/2 RT), and force-frequency relationship by the end of this research. The current study demonstrated a detrimental effect of DOX on skeletal performance as evidenced by a significant increase in CT and 1/2 RT compared to control; in addition, H 2 O 2 , TNF-α, and HOMA-IR were significantly increased with a significant decrease in GLUT4 expression and catalase activity. Combined exercise therapy showed a remarkable improvement in skeletal muscle performance, compared to DOX, CT, and 1/2 RT which were significantly decreased; H 2 O 2 and TNF-α were significantly decreased unlike catalase antioxidant activity that significantly increased; in addition, skeletal muscle glucose metabolism was significantly improved as GLUT4 expression significantly increased and HOMA-IR was significantly decreased. Exercise therapy showed significant improvement in all measured parameters relative to DOX. However, combined exercise therapy showed the best improvement relative to both pre-exercise and post-exercise groups.

Ameliorative Effects of Zinc Oxide, in Either Conventional or Nanoformulation, Against Bisphenol A Toxicity on Reproductive Performance, Oxidative Status, Gene Expression and Histopathology in Adult Male Rats - Dina M. M. H. El-Kossi; Shawky S. Ibrahim; Kamel M. A. Hassanin; Nashwa Hamad; Noha A. Rashed; Ahmed Abdel-Wahab (Biological Trace Element Research, 2024)
Bisphenol A (BPA) is a widely used endocrine disruptor that represents a significant risk to male reproductive function. Zinc (Zn) is vital for appropriate development of testes and to guarantee optimal testicular function and spermatogenesis. Our goal was to investigate if zinc oxide (ZnO), either in conventional or nanoformulation, could safeguard adult male rats’ reproductive performance against the damaging effects of BPA. Signaling expression of CYP11A1 and Nrf-2 in the testis, testicular oxidant-antioxidant status, Bax/Bcl-2 apoptotic ratio, and histological examination of various reproductive organs were all evaluated. Twenty-eight adult male albino rats were divided randomly into 4 groups (7 animals each) including the control, BPA, conventional zinc oxide (cZnO) + BPA, and zinc oxide nanoparticles (ZnO-NPs) + BPA groups. The study was extended for 2 successive months. Our findings revealed strong negative effects of BPA on sperm cell characteristics such as sperm motility, viability, concentration and abnormalities. Additionally, BPA reduced serum levels of testosterone, triiodothyronine (T3), and thyroxine (T4). Also, it evoked marked oxidative stress in the testes; elevating malondialdehyde (MDA) and reducing total antioxidant capacity (TAC). BPA significantly downregulated testicular mRNA relative expression levels of CYP11A1 and Nrf-2 , compared to control. Testicular apoptosis was also prompted by increasing Bax/ Bcl-2 ratio in testicular tissue. Histopathological findings in the testes, epididymis, prostate gland, and seminal vesicle confirmed the detrimental effects of BPA. Interestingly, cZnO and ZnO-NPs significantly alleviated all negative effects of BPA, but ZnO-NPs performed better. In conclusion, our findings point to ZnO, specifically ZnO-NPs, as a viable treatment for BPA-induced testicular dysfunction.

Empowering real-time flood impact assessment through the integration of machine learning and Google Earth Engine: a comprehensive approach - Nafis Sadik Khan; Sujit Kumar Roy; Swapan Talukdar; Mostaim Billah; Ashik Iqbal; Rashed Uz Zzaman; Arif Chowdhury; Sania B. Mahtab; Javed Mallick (Environmental Science and Pollution Research, 2024)

Effect of dietary electrolyte balance and arginine to lysine ratio on hematological, antioxidant and immunological traits in dual-purpose breeding hens under cyclic heat stress condition - Youssef A. Attia; Ahmed A. Abdallah; Fulvia Bovera; Abd El-Hamid E. Abd El-Hamid; Asmaa Sh El-Naggar; Rashed A. Alhotan; Vincenzo Tufarelli; Reda M. Zaki (Journal of Thermal Biology, 2024)

BDFLUX: A new bounded domain model for quantifying vertical fluxes in streambeds using heat as a tracer - Wenguang Shi; Quanrong Wang; Maria Klepikova; Dylan J. Irvine; Arwa Rashed; Zilong Liao (Journal of Hydrology, 2024)

Thermo-economic evaluation of a solar desalination equipped with Phase change material and spraying unit - Rashed Bahramei; Hadi Samimi-Akhijahani; Payman Salami; Naser Behroozi Khazaei (Desalination, 2024)

Spatiotemporal analyses of temperature and equivalent temperature and their relationship with crop health across Pakistan’s cropland - Muhammad Latif; Momel Zoon; Shahzada Adnan; Rehan Ahmed; Abdelwaheb Hannachi; Rashed Mahmood; Muhammad Umar (Theoretical and Applied Climatology, 2024)

Chamomile essential oil improves the growth, immunity, and antioxidant status of Nile tilapia exposed to nanosized alumina - Mayada R. Farag; Eman I. El Behery; Doaa S. Nouh; Youssef A. Attia; Rashed A. Alhotan; Mahmoud Alagawany; Alessandro Di Cerbo; Mona A Hassan (Aquaculture International, 2024)

New bithiophene derivative attenuated Alzheimer’s disease induced by aluminum in a rat model via antioxidant activity and restoration of neuronal and synaptic transmission - Kholoud AbdEl-Raouf; Hussein S.H. Farrag; Rashed Rashed; Mohamed A. Ismail; Monir A. El-Ganzuri; Wael M. El-Sayed (Journal of Trace Elements in Medicine and Biology, 2024)

Dietary flaxseed cake influences on performance, quality, and sensory attributes of eggs, serum, and egg trace minerals of laying hens - Youssef A. Attia; Ahmed A. Al-Sagan; El-Sayed O. S. Hussein; Marai J. Olal; Tarek A. Ebeid; Abdulaziz A. Al-Abdullatif; Rashed A. Alhotan; Salem R. Alyileili; Heba A. Shehata; Vincenzo Tufarelli (Tropical Animal Health and Production, 2024)

The path toward the 2030 Agenda: the implementation status of sustainable development goals in the large industrial sector of Bahrain - Abdulkarim Hasan Rashed (Environment, Development and Sustainability, 2024)

Cuticular chemical compounds of puparial cases of three forensically important blow flies from Egypt: potential for accurate identification and forensic investigations - Eman E. Zaher; Salwa S. Rashed; Fatma A. Abdel-Halim; Samar M. Mohammed; Abeer M. Salem (International Journal of Tropical Insect Science, 2024)
The distinct and species-specific chemical compounds found on the insect cuticle have demonstrated effectiveness in various applications, including species identification. Accurate identification of fly species becomes challenging when only damaged empty puparial cases are available, making it difficult to use traditional morphological and molecular identification methods. This study aimed to analyze the chemical compositions of puparial exuviae from three forensically and medically important fly species; Lucilia sericata , Chrysomya albiceps , and Chrysomya marginalis . Gas chromatography/mass spectrometry (GC–MS) was employed to assess the chemical profiles of these exuviae and evaluate their accuracy in identifying Dipteran insects. The study revealed the presence of twelve classes of chemical compounds across the three species, with retention times ranging from 18.78 to 35.03. A total of forty-two compounds with chain lengths ranging from C12 to C45 were identified. The profiles of Ch. albiceps and L. sericata displayed similarities, with alcohol being the most abundant compound (28.6%) in L. sericata . However, alkanes, including n-alkanes, branched alkanes, and cycloalkanes, constituted the main components of the cuticles in the three species, with Ch. marginalis displaying the highest percentage. These findings represent an initial step towards utilizing hydrocarbon composition as a practical tool for distinguishing between forensic species in Egypt.

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

Protective influence of supplementary betaine against heat stress by regulating intestinal oxidative status and microbiota composition in broiler chickens - Ali R. Al Sulaiman; Ala M. Abudabos; Rashed A. Alhotan (International Journal of Biometeorology, 2024)

Yucca schidigera Extract Mitigates the Oxidative Damages, Inflammation, and Neurochemical Impairments in the Brains of Quails Exposed to Lead - Mayada R. Farag; Seham El-Kassas; Youssef A. Attia; Rashed A. Alhotan; Mohamed A. Mahmoud; Alessandro Di Cerbo; Mahmoud Alagawany (Biological Trace Element Research, 2024)

Damage caused by Tetranychus urticae and Frankliniella occidentalis on rose plant: effect of different initial population densities - Samaneh Yari; Hamidreza Hajiqanbar; Yaghoub Fathipour; Azadeh Farazmand; Arash Rashed (Arthropod-Plant Interactions, 2024)

Linking green supply chain management practices and environmental performance in the manufacturing industry: a hybrid SEM-ANN approach - Rashed Al Karim; Mohammad Rokibul Kabir; Md Karim Rabiul; Sakia Kawser; Abdus Salam (Environmental Science and Pollution Research, 2024)

From source to house: unraveling the seasonal effect of water distribution system on drinking water quality of poultry farms under Egyptian environmental condition - Mohammed Abdelhameed Kamal; Rashed A. Alhotan; Ali R. Al Sulaiman; Elsayed Osman Hussein; Branislav Galik; Ahmed Ali Saleh (Environmental Science and Pollution Research, 2024)

Improved performance of land-fixed oscillating water column through dual chamber design - Heath Palmer; Ming Zhao; Helen Wu; Pan Hu; Mohammad Rashed Mia; Chengwang Lei (Ocean Engineering, 2023)

A numerical assessment of the dispersion of dissolved pollutants in the Arabian Gulf associated with the Barakah nuclear power plant - Oleksandr Nesterov; Yacine Addad; Sana Bilal; Emmanuel Bosc; Rachid Abida; Maryam Rashed Al Shehhi; Marouane Temimi (Ocean Modelling, 2023)

What drives carbon stocks in a mangrove forest? The role of stand structure, species diversity and functional traits - Md. Rashed Zaman; Md. Saidur Rahman; Shamim Ahmed; Pieter A. Zuidema (Estuarine, Coastal and Shelf Science, 2023)

Correction to: Mapping of dressed and processed poultry products in Bangladesh: Identifying the food safety risks for policy intervention - Jinnat Ferdous; Helal Uddin; Rashed Mahmud; Mathew Hennessey; Abdullah Al Sattar; Suman Das Gupta; Justine S. Gibson; Robyn Alders; Joerg Henning; Guillaume Fournié; Ahasanul Hoque (Veterinary Research Communications, 2023)

Mapping of dressed and processed poultry products in Bangladesh: Identifying the food safety risks for policy intervention - Jinnat Ferdous; Md Helal Uddin; Rashed Mahmud; Mathew Hennessey; Abdullah Al Sattar; Suman Das Gupta; Justine S. Gibson; Robyn Alders; Joerg Henning; Guillaume Fournié; Md. Ahasanul Hoque (Veterinary Research Communications, 2023)
Bangladesh’s commercial poultry production is growing rapidly, including the commercial processing of poultry. This expansion of poultry processing plants is fueled by the belief that this sub-sector provides safer food and has less food-borne disease risks compared to traditional live bird markets (LBMs). The purpose of this study is to describe Bangladesh’s dressed and processed poultry production and distribution network (PDN), identify what and where quality control occurs, and suggest where improvements could be made. Engaging with PDN for dressed and processed poultry, we used in-depth interviews with key informants to identify the stakeholders involved and their connections with other poultry PDNs. In addition, we mapped out the supply and distribution of dressed and processed poultry and quality control processes occurring throughout the network. We argue that dressed and processed poultry PDNs are closely connected with traditional PDNs such as LBMs, with multiple crossover points between them. Also, there is a lack of consistency in quality control testing and a lack of meat traceability. Consequently, perceptions of dressed and processed poultry being safer than birds from LBMs needs to be treated with caution. Otherwise, unsubstantiated consumer confidence in dressed poultry may inadvertently increase the risk of food-borne diseases from these products.

A comprehensive overview of carbon dioxide, including emission sources, capture technologies, and the conversion into value-added products - Mohammed H. Eldesouki; Ahmed E. Rashed; Ahmed Abd El-Moneim (Clean Technologies and Environmental Policy, 2023)
Carbon dioxide is both the planet’s enemy and friend since it maintains the balance of the planet as this gas retains some of the radiant energy that the planet receives. Thus, it keeps the Earth’s heat, without which the Earth would be unbearably cold. However, the increase in the quantity of CO 2 in the Earth’s atmosphere contributes to the exacerbation of global warming. CO 2 is mainly produced from the processes of combustion of fuel and petroleum, as well as from the breathing process of living organisms. This study aims to provide a comprehensive view of carbon dioxide, including the main sources of emissions that resulted in negative effects, as well as the various ways to control these emissions by conducting a separation process during fuel combustion in power plants and preventing the release of large quantities into the atmosphere. Finally, an objective viewpoint on how to benefit from separated carbon dioxide and turn it into highly valuable products is presented. Given that this is a global problem that affects our planet, this review links other literature that deals with each part separately, and thus it presents a clear and comprehensive vision that enables the reader to be aware of carbon dioxide gas from all perspectives, concluding with future studies that are required to prevent an increase in negative effects in order to preserve the quality of life in our planet. Graphical abstract

Characterization and distribution of black rot disease causing pathogen-Xanthomonas campestris pv. campestris races of the Jeju Island, South Korea - Jeong-Eui Hong; Hee-Jin Kim; Mohammad Rashed Hossain; Mehede Hassan Rubel; Nihar Sahu; Sopheap Mao; Jong-Goo Kang; Hoy-Taek Kim; Masao Watanabe; Jong-In Park (Journal of Plant Pathology, 2023)

Cyclopia intermedia E. Mey protects against ROS-induced liver injury in HepG2/C3A cells. - Shanika Reddy; Khaled Rashed; Jeanine L. Marnewick; Fanie G. Rautenbach; Trevor Koekemoer; Maryna van de Venter (South African Journal of Botany, 2023)

CIMCA: Infusing computational intelligence in multi-criteria analysis to assess groundwater potential for recharge - Rashed Uz Zzaman; Muhammad Ali Nayeem; Sara Nowreen; Imran Hossain Newton; AKM Saiful Islam; Anwar Zahid; M. Sohel Rahman (Environmental Modelling & Software, 2023)

An in vivo study: Prebiotic evaluation of the resistant Starch from Metroxylon sagu on obesity using fat-induced rats - Mayrilyn Solo Thompson; Tan Hui Yan; Kathleen Michelle Mikal; Shafarin Mohammad Shamsudin; Aswir Rashed; Shahrul Razid Sarbini (Bioactive Carbohydrates and Dietary Fibre, 2023)

Performance of tubular microbial fuel cells using different industrial wastewater - Abdullah Almatouq; Mohd Elmuntasir Ahmed; Mishari Khajah; Hussain Abdullah; Rashed Al-Yaseen; Mariam Al-Jumaa; Farah Al-Ajeel; Ahmed Shishter (Journal of Water Process Engineering, 2023)

Green approach for sustainable production of paraffin fuel from CO2 hydrogenation on Fe-MOF catalyst - Hany E. Ahmed; Ahmed E. Rashed; Mohamed E. El-Khouly; Mohamed K. Albolkany; Ahmed Abd El-Moneim (Journal of Environmental Chemical Engineering, 2023)

Facile electrochemical anodisation for generating nanopores across visible light-responsive cerium-titanium oxide heterojunctions for environmental remediation - Milad Laghaei; Yichao Wang; Ahmed O. Rashed; Hossein Beladi; Lingxue Kong (Journal of Environmental Chemical Engineering, 2023)

Seroprevalence and associated risk factors for Toxoplasma gondii in water buffaloes (Bubalus bubalis) in Egypt - Abdelfattah Selim; Ayed Alshammari; Hattan S. Gattan; Mohammed H. Alruhaili; Gehan A. Rashed; Salma Shoulah (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Syngas to FCC-like gasoline range hydrocarbons with upgraded light olefin selectivity catalyzed by readily synthesized Fe-MOF - Ahmed E. Rashed; Marwa F. Elkady; Yoshihisa Matsushita; Alhassan Nasser; Ahmed Abd El-Moneim (Chemical Engineering Journal, 2023)

Exploiting fungi in bioremediation for cleaning-up emerging pollutants in aquatic ecosystems - Synan F. AbuQamar; Hassan I. Abd El-Fattah; Maha M. Nader; Rashed A. Zaghloul; Taia A. Abd El-Mageed; Samy Selim; Belal A. Omar; Walid F. Mosa; Ahmed M. Saad; Khaled A. El-Tarabily; Mohamed T. El-Saadony (Marine Environmental Research, 2023)

The application of graphene/h-BN metamaterial in medical linear accelerators for reducing neutron leakage in the treatment room - Mehdi Hassanpour; Marzieh Hassanpour; Mohammadreza Rezaie; Saeedeh Khezripour; Mohammad Rashed Iqbal Faruque; Mayeen Uddin Khandaker (Physical and Engineering Sciences in Medicine, 2023)

High prevalence of multidrug-resistant Campylobacter jejuni in sheep and goats milk in Jordan - Mohammad M. Obaidat; Rashed M. Alshdaifat (International Dairy Journal, 2023)

A reliability-based rock engineering system for clean blasting: risk analysis and dust emissions forecasting - Shahab Hosseini; Rashed Poormirzaee; Seyyed-Omid Gilani; Izhar Mithal Jiskani (Clean Technologies and Environmental Policy, 2023)

Major and trace element geochemistry of the Atrai River sediments from the Bengal Basin (Bangladesh): implication for provenance, chemical weathering, and tectonic setting in the southeastern Himalaya - Abu Sadat Md. Sayem; Md. Rokonuzzaman; Md. Shams Shahriar; Rashed Abdullah; Zahidul Bari; Md. Sazzad Hossen (Arabian Journal of Geosciences, 2023)

Novel concept for water scarcity quantification considering nonconventional and virtual water resources in arid countries: Application in Gulf Cooperation Council countries - Muhammad Al Rashed; Ahmed Sefelnasr; Mohsen Sherif; Ahmed Murad; Dalal Alshamsi; Amjad Aliewi; Abdel Azim Ebraheem (Science of The Total Environment, 2023)

Preparation and characterization of nanomuscovite by intercalation method for adsorption of heavy metals from polluted water - M. Nageeb Rashed; A. E Arifien; F. A. El-Dowy (Environmental Geochemistry and Health, 2023)
In this study, nanomuscovite adsorbents were prepared by intercalation with various organic intercalates (DTAB-TTAB-DTPA-PA-PN) and used to remove Cd 2+ and Pb 2+ from polluted water. The best nanomuscovite was prepared using DTPA and muscovite (Muc/DTPA) and characterized by XRD, TEM, EDX, FTIR, and BET surface area. The developed nanoadsorbent was used to remove Cd 2+ and Pb 2+ from polluted water. The effect of various factors, including contact time, adsorbent dosage, solution pH, and temperature, was investigated. The results reveal that the maximum adsorption of Cd 2+ and Pb 2+ was 91.5% and 97%, respectively, at the initial metal concentration 50 ppm, adsorbent dosage 0.2 g, contact time 60 min, solution temperature 25 °C, and pH 6 for Pb 2+ and pH 7 for Cd 2+ . Adsorption isotherm models (Freundlich, Langmuir, Dubunin–Radushkevich, and Temkin isotherm models) as well as kinetic models (pseudo-first-order, pseudo-second-order, Elovich, and intra-particle diffusion models) were employed to evaluate the experimental results. The adsorption of Cd 2+ and Pb 2+ on Muc/DTPA fitted well within the Langmuir isotherm model and followed pseudo-second-order kinetics. Thermodynamics parameters of metal adsorption indicated exothermic and spontaneous processes. Results were applied to the real wastewater that showed high Cd 2+ and Pb 2+ removal.

A robust optimization model for microgrid considering hybrid renewable energy sources under uncertainties - Hussain Haider; Yang Jun; Ghamgeen Izat Rashed; Fan Peixiao; Salah Kamel; Yonghui Li (Environmental Science and Pollution Research, 2023)

Dry-spun carbon nanotube ultrafiltration membranes tailored by anti-viral metal oxide coatings for human coronavirus 229E capture in water - Ahmed O. Rashed; Chi Huynh; Andrea Merenda; Julio Rodriguez-Andres; Lingxue Kong; Takeshi Kondo; Joselito M. Razal; Ludovic F. Dumée (Journal of Environmental Chemical Engineering, 2023)

Molecular docking and dynamics simulation approach of Camellia sinensis leaf extract derived compounds as potential cholinesterase inhibitors - Md. Eram Hosen; Md. Sojiur Rahman; Md Omar Faruqe; Md. Khalekuzzaman; Md. Asadul Islam; Uzzal Kumar Acharjee; Rashed Zaman (In Silico Pharmacology, 2023)

Synergistic role of resveratrol and exercise training in management of diabetic neuropathy and myopathy via SIRT1/NGF/GAP43 linkage - Reem Essam Ghoweba; Akef Abdelhalim Khowailed; Basma Emad Aboulhoda; Laila Ahmed Rashed; Asmaa Selmy (Tissue and Cell, 2023)

Investigation of pulsed electric field operation as a chemical-free anti-scaling approach for electrodialysis desalination of brackish water - Soraya Honarparvar; Rashed Al-Rashed; Amos G. Winter V. (Desalination, 2023)

Chemical Activation of Sludge from Drinking Water Treatment Plant for Adsorption of Methylene Blue Dye - Mohamed F. Soliman; M. Nageeb Rashed; Abeer Ali Ahmd (Water, Air, & Soil Pollution, 2023)
The objective of this study is to explore the preparation and application of sludge produced in plants of drinking water treatment, to remove methylene blue (MB) dye from polluted water. Adsorbate (methylene blue) is prepared in the lab. as a stock solution. To create new adsorbents, chemical activation of the used sludge has been carried out. The activation is performed by HCl and H 2 O 2 and a mixture of HCl and H 2 O 2 . The experiments were carried out under different boundary conditions, like the initial concentration of dye, dosage of adsorbent, solution pH, contact time, and temperature of the adsorption, to determine the optimum boundary conditions for operation. All of the experiments in this study were carried out in a batch system. The results show that sludge activation by a mixture of 2:1 HCl/ H 2 O 2 was selected as the best chemically activated adsorbent (removal of 99.9%). For the best MB adsorption results, the following criteria must be met: 50 ppm initial dye concentration, 90 min of contact time, pH 7, and a dosage of 0.25 g of the adsorbent. Adsorbents suit the Langmuir and Freundlich models well, according to applications of the Freundlich Isotherm and Langmuir models.

Characterization and phylogenetic analysis of the complete mitochondrial genome of Mango tilapia (Sarotherodon galilaeus: Cichlidae) - Yosur G. Fiteha; M. A. Rashed; R. A. M. Ali; M. Magdy (Molecular Biology Reports, 2023)
Background Sarotherodon galilaeus (Linné, 1758) is a member of the family Cichlidae, which is considered the most important aquaculture freshwater species endemic to Africa and the Middle East. The genetics and molecular biology of this species are rare. This requires more comprehensive mitochondrial genomes-based phylogenetics to enhance understanding of the relationship and delineate this species. Methods and results Here, we assembled the complete mitogenome of S. galilaeus using Illumina high-throughput sequencing technology. The mango tilapia mitogenome was 16,631 bp in length with an AT composition of 53.4% and 46.4% GC content. It encodes 37 genes comprising two ribosomal RNA genes (rRNAs), 22 transfer RNA genes (tRNAs), and 13 protein-coding genes (PCGs) as well as the D-loop known as the control region. The phylogenetic tree was conducted to provide a relationship within the haplotilapiine lineage based on the maximum likelihood method, and the newly sequenced S. galilaeus was clustered with other Sarotherodon species. Conclusion Our results provide a new perception of the genetic basis of S . galilaeus species for further research on systematics, evolution, population genetics, and molecular ecology.

An eco-sustainable approach towards heavy metals remediation by mangroves from the coastal environment: A critical review - Krishna Kumar Yadav; Neha Gupta; Shiv Prasad; Lal Chand Malav; Javed Khan Bhutto; Akil Ahmad; Amel Gacem; Byong-Hun Jeon; Ahmed M. Fallatah; Basim H. Asghar; Marina M.S. Cabral-Pinto; Nasser S. Awwad; et al. (Marine Pollution Bulletin, 2023)

The waste heat of a biofuel-powered SOFC for green hydrogen production using thermochemical cycle; Economic, environmental analysis, and tri-criteria optimization - Abdulwahab A. Alnaqi; Jalal Alsarraf; Abdullah A.A.A. Al-Rashed (Fuel, 2023)

Multi-objective optimization of shading devices using ensemble machine learning and orthogonal design of experiments - Rashed Alsharif; Mehrdad Arashpour; Emad Golafshani; Ali Rashidi; Heng Li (Energy and Buildings, 2023)

Hydrogen sulfide alleviates acrylamide-induced testicular toxicity in male rats - Hamada Ahmed Mokhlis; Mohammed Helmy Rashed; Ibrahim Ghalib Saleh; Mahmoud Gomaa Eldeib; Ahmed A. El-Husseiny; Emad Gamil Khidr; Maher H. Gomaa; Hesham S. Gad; Ahmed Aglan (Toxicology and Environmental Health Sciences, 2023)

A comprehensive investigation of performance of pulsed electrodialysis for desalination of brackish water - Soraya Honarparvar; Rashed Al-Rashed; Amos G. Winter V. (Desalination, 2023)

Electrocatalytic ultrafiltration membrane reactors designed from dry-spun self-standing carbon nanotube sheets - Ahmed O. Rashed; Chi Huynh; Andrea Merenda; Si Qin; Maxime Maghe; Lingxue Kong; Takeshi Kondo; Joselito M. Razal; Ludovic F. Dumée (Chemical Engineering Journal, 2023)

Sustainability Information Provision (SIP) framework: A review of the promotion of sustainability in the residential sector - Yussra Rashed; Sara Omrani; Danie Nilsson; Robin Drogemuller (Building and Environment, 2023)

Estimation of the piled embankment critical height: a systematic review - Nooran Mohamed Edries; Mohamed Ezzat Al-Atroush; Ahmed Rashed; Sayed M. Ahmed (Innovative Infrastructure Solutions, 2023)

The impact of PET microplastic fibres on PVDF ultrafiltration performance – A short-term assessment of MP fouling in simple and complex matrices - Cyril Hachemi; Marie Enfrin; Ahmed O. Rashed; Veeriah Jegatheesan; Peter D. Hodgson; Damien L. Callahan; Judy Lee; Ludovic F. Dumée (Chemosphere, 2023)

GPR ringing suppression using lateral outliers' swap filter - Ali H. Atef; Mohamed A. Rashed (Journal of Applied Geophysics, 2023)

A comparative investigation of syngas and biofuel power and hydrogen plant combining nanomaterial-supported solid oxide fuel cell with vanadium-chlorine thermochemical cycle - Abdullah A.A.A. Al-Rashed; Jalal Alsarraf; Abdulwahab A. Alnaqi (Fuel, 2023)

Efficiency of TiO2/Fe2NiO4 Nanocomposite in Photocatalytic Degradation of Acid Orange 7 (AO7) Under UV Irradiation - Inshad Jum’h; Rashed Abu-Aleqa; Rami Jumah; Carlos J. Tavares; Ahmad Telfah (Water, Air, & Soil Pollution, 2023)

Mesenchymal Stem Cells and Selenium Nanoparticles Synergize with Low Dose of Gamma Radiation to Suppress Mammary Gland Carcinogenesis via Regulation of Tumor Microenvironment - Omayma A. R. Abozaid; Laila A. Rashed; Sawsan M. El-Sonbaty; Amira I. Abu-Elftouh; Esraa S. A. Ahmed (Biological Trace Element Research, 2023)
Breast cancer is one of the most prevalent and deadliest cancers among women in the world because of its aggressive behavior and inadequate response to conventional therapies. Mesenchymal stem cells (MSCs) combined with green nanomaterials could be an efficient tool in cell cancer therapy. This study examined the curative effects of bone marrow–derived mesenchymal stem cells (BM-MSCs) with selenium nanoparticles (SeNPs) coated with fermented soymilk and a low dose of gamma radiation (LDR) in DMBA-induced mammary gland carcinoma in female rats. DMBA-induced mammary gland carcinoma as marked by an elevation of mRNA level of cancer promoter genes (Serpin and MIF, LOX-1, and COL1A1) and serum level of VEGF, TNF-α, TGF-β, CA15-3, and caspase-3 with the reduction in mRNA level of suppressor gene (FST and ADRP). These deleterious effects were hampered after treatment with BM-MSCs (1 × 10 6 cells/rat) once and daily administration of SeNPs (20 mg/kg body weight) and exposure once to (0.25 Gy) LDR. Finally, MSCs, SeNPs, and LDR notably modulated the expression of multiple tumor promoters and suppressor genes playing a role in breast cancer induction and suppression.

aroF and cm2: potential molecular markers for the detection of stone-inhabiting Actinobacteria on cultural heritage sites - Samah Mohamed Rizk; Mahmoud Magdy; Filomena De Leo; Olaf Werner; Mohamed Abdel-Salam Rashed; Rosa María Ros; Clara Urzì (Archives of Microbiology, 2023)

Characterizing the Vs Profile from Surface Wave Data Using a Customized Artificial Jellyfish Search Algorithm - Rashed Poormirzaee; Alireza Kabgani (Pure and Applied Geophysics, 2022)

Effects of a novel probiotic mixture on the modulation of brain and intestine Aquaporin-4 gene expression in rats exposed to Cadmium - Saba Sadeghi Rashed; Mehran Ghaffari; Nahid Beladi Moghadam; Maryam Tajabadi Ebrahimi; Zahra Keshtmand (Metabolic Brain Disease, 2022)

Hydrodynamic Performance of a Floating Offshore Oscillating Water Column Wave Energy Converter - Mohammad Rashed Mia; Ming Zhao; Helen Wu; Vatsal Dhamelia; Pan Hu (Journal of Marine Science and Engineering, 2022)
A floating oscillating water column (OWC) wave energy converter (WEC) supported by mooring lines can be modelled as an elastically supported OWC. The main objective of this paper is to investigate the effects of the frequency ratio on the performance of floating OWC (oscillating water column) devices that oscillate either vertically or horizontally at two different mass ratios (m = 2 and 3) through two-dimensional computational fluid dynamics simulations. The frequency ratio is the ratio of the natural frequency of the system to the wave frequency. Simulations are conducted for nine frequency ratios in the range between 1 and 10. The hydrodynamic efficiency achieves its maximum at the smallest frequency ratio of 1 if the OWC oscillates horizontally and at the largest frequency ratio of 10 if the OWC oscillates vertically. The frequency ratio affects the hydraulic efficiency of the vertical oscillating OWC significantly stronger than that of the horizontal oscillating OWC, especially when it is small. The air pressure and the volume oscillation in OWC is not affected much by the horizontal motion of the OWC but is significantly affected by the vertical motion, especially at small frequency ratios.

Abundance, characteristics, and spatial–temporal distribution of microplastics in sea salts along the Cox’s Bazar coastal area, Bangladesh - Muhammad Saiful Islam; Md. Rashed Hasan; Zahidul Islam (Environmental Science and Pollution Research, 2022)

Rainfall and sea-level variability in the face of changing El Niño: evidence from the U.S.-affiliated Pacific islands - Md. Rashed Chowdhury; Pao-Shin Chu; Ousmane Ndiaye; James T. Potemra (Meteorology and Atmospheric Physics, 2022)

Infectious Pepper Mild Mottle Virus and Human Adenoviruses as Viral Indices in Sewage and Water Samples - Mohammed Kamal Rashed; Waled Morsy El-Senousy; ElSayed Tarek Abd ElSalam Sayed; Maha AlKhazindar (Food and Environmental Virology, 2022)
The objective of this study was to compare human adenoviruses (HAdVs) genome and infectivity, polyomaviruses (JC and BK) genome (JCPyVs) and (BKPyVs), Pepper Mild Mottle Virus (PMMoV) genome and infectivity, and infectious bacteriophages as viral indices for sewage and water samples. One hundred and forty-four samples were collected from inlets and outlets of water and wastewater treatment plants (WTPs), and WWTPs within Greater Cairo from October 2015 till March 2017. Two methods of viral concentration [Aluminium hydroxide (Al(OH) 3 ) precipitation method and adsorption-elution technique followed by organic flocculation method] were compared to determine which of them was the best method to concentrate viruses from sewage and water. Although samples with only one litre volume were concentrated using Al(OH) 3 precipitation method and the same samples with larger volumes (5–20 L) were concentrated using the adsorption-elution technique followed by the organic flocculation method, a non-significant difference was observed between the efficiency of the two methods in all types of samples except for the drinking water samples. Based on the qualitative prevalence of studied viruses in water and wastewater samples, the number of genome copies and infectious units in the same samples, resistance to treatment processes in water and wastewater treatment plants, higher frequency of both adenoviruses and PMMoV genomes as candidate viral indices in treated sewage and drinking water was observed. The problem of having a viral genome as indices of viral pollution is that it does not express the recent viral pollution because of the longer survivability of the viral genome than the infectious units in water and wastewater. Both infectious adenovirus and infectious phiX174 bacteriophage virus showed similar efficiencies as indices for viral pollution in drinking water and treated sewage samples. On the other hand, qualitative detection of infectious PMMoV failed to express efficiently the presence/absence of infectious enteric viruses in drinking water samples. Infectious adenoviruses and infectious bacteriophage phiX174 virus may be better candidates than adenoviruses genome, polyomaviruses genome, and PMMoV genome and infectivity as viral indices for water and wastewater.

Assessment of radiometric hazards in the Southern Industrial Zone, Jeddah City, using car-borne gamma-ray spectrometry system - Hussein M. Harbi; Helmy S. Abuenaga; Mohamed A. Rashed; Ali H. Atef (Arabian Journal of Geosciences, 2022)

Stock Assessment of Six Sciaenidae Species in the Bay of Bengal, Bangladesh Water Using a Length-Based Bayesian Biomass (LBB) Method - Rokeya Sultana; Qun Liu; Petra Schneider; Md. Abdullah Al-Mamun; Al Mamun; Md. Farhan Tazim; Mohammad Mojibul Hoque Mozumder; Mohammed Rashed Parvej; Md. Mostafa Shamsuzzaman (Fishes, 2022)
Six most abundant and commercially valuable croakers (Sciaenidae) stocks in the coastal water of Bangladesh were evaluated using a length-based Bayesian Biomass (LBB) approach. The ratios B/B0 (current relative biomass) were smaller than the BMSY/B0 in five of the six stocks. For the six estimated populations, two (Otolithes ruber and Pterotolithus maculatus) are grossly overfished, one (Otolithoides pama) is overfished, two (Johnius belangerii and Panna heterolepis) are slightly overfished, and only donkey croaker (Pennahia anea) is in the healthy (B/B0 > BMSY/B0) status. Furthermore, the optimal length at first capture (Lc_opt) was higher than the length at first capture (Lc) in four populations, indicating growth overfishing, suggesting that increasing mesh size would benefit the catch and biomass. Findings from the present study confirm the declining trend of fisheries resources, particularly the croaker species in the BoB, Bangladesh coastal water. Management strategies (such as effort control, choosing the appropriate mesh size, total allowable catch limit, identify and enhance protection of the feeding, breeding, and nursery ground, etc.) should be taken for the sustainable management and recovery of the country’s marine fishing resources, particularly the valuable croaker species.

Abdominoplasty Panniculus as a Source for Human Acellular Dermis: A Preliminary Report - Nayef Abdulrahman. Louri; Nigamananda Dey; Rashed N. AlHasan; Safa Hassan Abdulla; Mohamed Elsakka; Rasheeqa Gulreez; Abdulla Hassan Darwish; Balamuthu Kadalmani; Khalid Bin Ali Al Khalifa (Tissue Engineering and Regenerative Medicine, 2022)

Four new phenolics and antiparasitic secondary metabolites from Flacourtia rukam Zoll. & Mortizi - Naglaa I. Afifi; Abeer S. Moawad; Mohamed A. Zaki; Mostafa E. Rateb; Mohammed H. Rashed; Ibrahim G. Saleh; Mona H. Hetta; Rabab M. Mohammed (Natural Product Research, 2022)

Climate change vulnerability in Bangladesh based on trend analysis of some extreme temperature indices - Istiak Ahmed; Sheikh Ishtiaque; Taslima Zahan; Md. Saif Uddin Rashed; Ranjit Sen; Md. Faruque Hossain; Shyamal Brahma; Imrul Mosaddek Ahmed; M. Akhtar Hossain; Mohammad Akkas Ali; Abu Hena Sorwar Jahan; Sheikh Imtiaz; et al. (Theoretical and Applied Climatology, 2022)

An ANN-Fuzzy Cognitive Map-Based Z-Number Theory to Predict Flyrock Induced by Blasting in Open-Pit Mines - Shahab Hosseini; Rashed Poormirzaee; Mohsen Hajihassani; Roohollah Kalatehjari (Rock Mechanics and Rock Engineering, 2022)
Blasting is widely employed as an accepted mechanism for rock breakage in mining and civil activities. As an environmental side effect of blasting, flyrock should be investigated precisely in open-pit mining operations. This paper proposes a novel integration of artificial neural network and fuzzy cognitive map (FCM) with Z -number reliability information to predict flyrock distance in open-pit mine blasting. The developed model is called the artificial causality-weighted neural networks, based on reliability (ACWNNsR). The reliability information of Z -numbers is used to eliminate uncertainty in expert opinions required for the initial matrix of FCM, which is one of the main advantages of this method. FCM calculates weights of input neurons using the integration of nonlinear Hebbian and differential evolution algorithms. Burden, stemming, spacing, powder factor, and charge per delay are used as the input parameters, and flyrock distance is the output parameter. Four hundred sixteen recorded basting rounds are used from a real large-scale lead–zinc mine to design the architecture of the models. The performance of the proposed ACWNNsR model is compared with the Bayesian regularized neural network and multilayer perceptron neural network and is proven to result in more accurate prediction in estimating blast-induced flyrock distance. In addition, the results of a sensitivity analysis conducted on effective parameters determined the spacing as the most significant parameter in controlling flyrock distance. Based on the type of datasets used in this study, the presented model is recommended for flyrock distance prediction in surface mines where buildings are close to the blasting site.

Ag nanoparticle-decorated chitosan/SrSnO3 nanocomposite for ultrafast elimination of antibiotic linezolid and methylene blue - M. Faisal; Md Abu Rashed; Jahir Ahmed; Mabkhoot Alsaiari; Mohammed Jalalah; Saeed A. Alsareii; Farid A. Harraz (Environmental Science and Pollution Research, 2022)

Green building aspects in Bangladesh: A study based on experts opinion regarding climate change - Md. Arif Chowdhury; Hasnat Sabrina; Rashed Uz Zzaman; Syed Labib Ul Islam (Environment, Development and Sustainability, 2022)

Genetic diversity of Iranian wild barley (Hordeum spontaneum Koch.) populations - Mojtaba Hosseini; Mohsen Yassaie; Mohammad Hassan Rashed-Mohassel; Reza Ghorbani; Ali Niazi (Journal of Crop Science and Biotechnology, 2022)

Comments on “Workplace violence among healthcare workers during COVID-19 pandemic in a Jordanian governmental hospital: the tip of the iceberg” by El-Shafei, D. A. et al., 2021 (10.1007/s11356-021–15112-w) - Moustaq Karim Khan Rony; Rashed Ullah Rana (Environmental Science and Pollution Research, 2022)

Association of Gut Microbiota with Inflammatory Bowel Disease and COVID-19 Severity: A Possible Outcome of the Altered Immune Response - Anju Kaushal; Rashed Noor (Current Microbiology, 2022)

Groundwater modelling approach for efficient governance of transboundary aquifers with Kuwait - Amjad Aliewi; Muhammed Al-Rashed (Arabian Journal of Geosciences, 2022)

Study of the effectiveness of landfill final cover in reducing BTEX emissions - Abderrahim Lakhouit; Wael S. Al-Rashed (Arabian Journal of Geosciences, 2022)

Potential aptitude of four olive cultivars as anticancer and antioxidant agents: oleuropein content - Shimaa A. Rashed; Tamannouha I. Saad; Salama M. El-Darier (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)
Olea europaea L. (olive, Oleaceae) constitutes a source of many bioactive compounds, which have recognized benefits for both human health and technological purposes. The present article was carried out to evaluate the biological activity of oleuropein (an ester of 2-(3,4-dihydroxyphenyl) ethanol (hydroxytyrosol) which has the oleosidic skeleton that is common to the secoiridoid glucosides of Oleaceae). It occurred in leaf extracts of the four olive cultivars (Chemlali, Manzanilla, Picaul and Toffahi) as a source for some anticancer and antioxidant agents and their consequences on the action of Hordeum vulgare (barley). The total phenolic and flavonoid compounds were extracted from olive leaves by ethanol 95% then analyzed by high-performance liquid chromatography (HPLC). The study evaluates the anticancer activity of the ethanolic extract of olive leaves against breast and hepatocellular carcinoma cells showing high values. Also, the extract exhibited highly consequence on the antioxidant potentiality of barley which was assessed using the diphenyl picryl hydrazyl method (DDPH). These results pave the way for utilization of olive leaves as a source of natural anticancer and antioxidant agents.

How does tourist perception lead to tourist hesitation? Empirical evidence from Bangladesh - Mohammad Rashed Hasan Polas; Ratul Kumar Saha; Mosab I. Tabash (Environment, Development and Sustainability, 2022)

Functionalized multi-walled carbon nanotubes for oil spill cleanup from water - Thamer Adnan Abdullah; Tatjana Juzsakova; Sanaa A. Hafad; Rashed Taleb Rasheed; Noor Al-Jammal; Muhammad Ali Mallah; Ali Dawood Salman; P. C. Le; Endre Domokos; Mustafa Aldulaimi (Clean Technologies and Environmental Policy, 2022)
The growing global economy resulted in an incessant increase in transportation and exploitation of oil. Hence, the oil spillage has been considered a serious threat to aquatic and terrestrial ecosystems. Therefore, water purification has been considered a major challenge around the world. There are numerous classical methods available for oil removal from water, but owing to multiple defects and disadvantages, research efforts have focused to find such adsorbents which can improve oil adsorption capability. Traditional adsorbent material typically applied in oil removal includes activated carbon, organoclays, wool, zeolites, etc. These materials suffer from several drawbacks such as low absorption capacity, non-selective absorption, and complicated reusability, whereas nano-adsorbents offer multiple advantages such as having multiple sorption sites, large surface area, short intra-particle diffusion distance, tuneable pore size, and ease of low-temperature modification. Multi-walled carbon nanotubes (MWCNTs) are extensively used adsorbent materials with a strong affinity for the removal of organic pollutants. The functionalization MWCNTs further increase the sorption capacity of adsorbents manifolds to remove organic materials. These nanocomposites are also compatible with green materials and considered environmentally friendly adsorbents. This review paper aims at providing an insight to understand the properties of the MWCNTs and their potential use to adsorb hydrocarbons from water. Moreover, the synthesis methods of those materials, their modification procedures including the functionalization with metal oxide nanoparticles, and applications are also discussed in detail. Graphic abstract

Cytotoxic and anti-diabetic potential, metabolic profiling and insilico studies of Syzygium cumini (L.) Skeels belonging to family Myrtaceae - Seham Salah Eldin Elhawary; Amira kamal Eldin Elmotayam; Doaa kamel Alsayed; Eman Maher Zahran; Merivat Ahmed Fouad; Amany Ameen Sleem; Hanan Elimam; Mohamed H. Rashed; Alaa M. Hayallah; Anber F. Mohammed; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

Spatial variability of climatic hazards in Bangladesh - Md. Arif Chowdhury; Rashed Uz Zzaman; Nusrat Jahan Tarin; Mohammad Jobayer Hossain (Natural Hazards, 2022)

A Machine Learning-based Approach for Groundwater Mapping - Rashed Uz Zzaman; Sara Nowreen; Irtesam Mahmud Khan; Md. Rajibul Islam; Nabil Ibtehaz; M. Saifur Rahman; Anwar Zahid; Dilruba Farzana; Afroza Sharmin; M. Sohel Rahman (Natural Resources Research, 2022)

The impact of Rumex vesicarius seed water extracts on mice fertility - Ahmad Rashed Alhimaidi; Aiman Abdullah. Ammari; Mohammad Khair Okla; Muath Qasem Algadi; Ramzi Ahmed Amran; Hissah Ibrahim Alhusayni; Mohammed Ahmad Alhimaidi (Environmental Science and Pollution Research, 2022)
Rumex vesicarius (RV) is an edible wild annual plant, and it is reported that it contains a good source of minerals, protein, and ascorbic acid. Several studies have indicated the anti-liver damage, anticancer, antimicrobial, and antioxidant properties of the RV plant. There are currently no reports regarding the effect of RV on fertility. Therefore, this study focuses on the impact of RV water seed extracts on mice fertility. RV plants were collected, and water seed extracts were prepared; 50 mg/kg body weight (BW) of this was then injected into the mice (male and female) using an oral feeding tube 5 days before mating (group I) or during caging of the females with the males for 1 week to detect their fertility rate. In the different female groups, no significant difference between their BW and their newborn’s BW in the treated and control groups was found. Female fertility, pregnancy, and offspring rates showed some variation within each female group and between the different female groups. In comparing the fertility and offspring rate between the different groups, there was a significant difference ( P < 0.05) between groups I and III females and between groups I and IV females, while the other groups showed no significant differences. In contrast, the other groups showed no significant differences. Regarding the impact of the water seed extract on males, the BW was approximately the same in control and treated males.

Seed germination and seedling emergence in two populations of eastern dodder (Cuscuta monogyna Vahl.): evaluation of environmental factors and burial depth - Esmail Ebrahimi; Ebrahim Izadi Darbandi; Mohammad Hassan Rashed Mohassel; Reza Tavakol Afshari (Acta Physiologiae Plantarum, 2022)

Antimicrobial and synergistic effect of Moroccan native Argania spinosa essential oil for modulating of antibiotics resistance - Ahmed Nafis; Lahcen Hassani; Najat Marraiki; Sarah Al-Rashed; Abdallah M. Elgorban; Asad Syed; Marcello Iriti (Natural Product Research, 2021)

Natural radioactivity levels in benthic foraminifera Sorites marginalis as a pollution indicator - Wafaa Rashed; Khaled Salahel Din; Mohamed Youssef (Isotopes in Environmental and Health Studies, 2021)

Possible role of rice bran extract in microglial modulation through PPAR-gamma receptors in alzheimer’s disease mice model - Shimaa Saad El-Din; Sahar Abd Elwahab; Laila Rashed; Salwa Fayez; Basma Emad Aboulhoda; Ola Ahmed Heikal; Asmaa Fathi Galal; Zeinab A. Nour (Metabolic Brain Disease, 2021)

Investigation of landfill leachate pollution impact on shallow aquifers using numerical simulation - Amjad Aliewi; Khaled Hadi; Harish Bhandary; Habib Al-Qallaf; Tareq Rashed; Ahmed Abdulhadi; Sultan Majed Al-Salem (Arabian Journal of Geosciences, 2021)

Evolutionary computing of the compression index of fine-grained soils - Saif Alzabeebee; Younis M. Alshkane; Kamal Ahmad Rashed (Arabian Journal of Geosciences, 2021)

COVID-19 Pandemic and the Convalescent Plasma Therapy: Possible Benefits and Risks - Rashed Noor; Nishat Tasnim; Chandrika Saha (Current Clinical Microbiology Reports, 2021)

A Review on the Effectivity of the Current COVID-19 Drugs and Vaccines: Are They Really Working Against the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Variants? - Rashed Noor (Current Clinical Microbiology Reports, 2021)

Developmental Status of the Potential Vaccines for the Mitigation of the COVID-19 Pandemic and a Focus on the Effectiveness of the Pfizer-BioNTech and Moderna mRNA Vaccines - Rashed Noor (Current Clinical Microbiology Reports, 2021)

Modulation of vigabatrin induced cerebellar injury: the role of caspase-3 and RIPK1/RIPK3-regulated cell death pathways - Marwa Abd El-kader; Eman Hamza; Randa El-Gamal; Amira Sobhy Rashed Eladl; Eman Mohamad El Nashar; Mansour A. Alghamdi; Omnia S. Erfan (Journal of Molecular Histology, 2021)

A Roadmap for Policy-Relevant Sea-Level Rise Research in the United Arab Emirates - Hannah Melville-Rea; Clare Eayrs; Nasser Anwahi; John A. Burt; Denise Holland; Fatin Samara; Francesco Paparella; Ahmed Hassan Al Murshidi; Maryam Rashed Al-Shehhi; David M. Holland (Frontiers in Marine Science, 2021)
The United Arab Emirates (UAE) has a long-term policy horizon, the financial capital, and a vision for a sustainable knowledge-based economy. These characteristics uniquely situate it as a potential leader for sea-level rise research. Climate science is already growing, and at the center of the UAE's pivot toward climate research is a burgeoning concern for sea-level rise. Over 85% of the UAE's population and more than 90% of the nation's infrastructure is within a few meters of present-day sea-level. With its low-lying and shallow-sloping geography (about 35 cm per km), this high-value coastline, including the rapidly expanding cities of Dubai and Abu Dhabi, is particularly vulnerable to sea-level rise. Meanwhile, limited regional research and data scarcity create deep uncertainty for sea-level projections. We set out a potential roadmap for the UAE to capitalize on its strengths to create usable and relevant sea-level projections for the region. With a newly established Climate Change Research Network, the UAE government is beginning to draw together universities and research centers for “furthering effective data collection and management, and advancing policy-relevant research on climate impacts and adaptation 1 .” By consolidating ideas from the science community within the UAE, we identify promoters and barriers to data gathering, information sharing, science-policy communication, and funding access. Our paper proposes pathways forward for the UAE to integrate sea-level science with coastal development and form best practices that can be scaled across climate science and throughout the region.

Whole-genome sequencing of Egyptian multidrug-resistant Klebsiella pneumoniae isolates: a multi-center pilot study - May Sherif; Mattia Palmieri; Caroline Mirande; Hadir El-Mahallawy; Hebatallah G. Rashed; Fadwa Abd-El-Reheem; Arwa Ramadan El-Manakhly; Radwa Ahmad Rabea Abdel-latif; Aliaa Gamaleldin Aboulela; Laila Yosef Saeed; Soheir Abdel-Rahman; Eman Elsayed; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

The occurrence and dietary intake related to the presence of microplastics in drinking water in Saudi Arabia - Lama Almaiman; Alaa Aljomah; Mohammed Bineid; Futoon M. Aljeldah; Fahad Aldawsari; Bettina Liebmann; Ievgeniia Lomako; Katharina Sexlinger; Rashed Alarfaj (Environmental Monitoring and Assessment, 2021)

The sustainability–peace nexus in crisis contexts: how the Rohingya escaped the ethnic violence in Myanmar, but are trapped into environmental challenges in Bangladesh - Saleh Ahmed; William Paul Simmons; Rashed Chowdhury; Saleemul Huq (Sustainability Science, 2021)

Study on Urinary Candidate Metabolome for the Early Detection of Breast Cancer - Faten Zahran; Ramzy Rashed; Mohamed Omran; Hossam Darwish; Arafa Belal (Indian Journal of Clinical Biochemistry, 2021)

A comparative review of pathogenesis and host innate immunity evasion strategies among the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), severe acute respiratory syndrome coronavirus (SARS-CoV) and the Middle East respiratory syndrome coronavirus (MERS-CoV) - Rashed Noor (Archives of Microbiology, 2021)

The influence of COVID-19 preventive measures on the air quality in Abu Dhabi (United Arab Emirates) - Oriol Teixidó; Aurelio Tobías; Jordi Massagué; Ruqaya Mohamed; Rashed Ekaabi; Hussein I. Hamed; Richard Perry; Xavier Querol; Shaikha Al Hosani (Air Quality, Atmosphere & Health, 2021)
The preventive and cautionary measures taken by the UAE and Abu Dhabi governments to reduce the spread of the coronavirus disease (COVID-19) and promote social distancing have led to a reduction of mobility and a modification of economic and social activities. This paper provides statistical analysis of the air quality data monitored by the Environment Agency – Abu Dhabi (EAD) during the first 10 months of 2020, comparing the different stages of the preventive measures. Ground monitoring data is compared with satellite images and mobility indicators. The study shows a drastic decrease during lockdown in the concentration of the gaseous pollutants analysed (NO 2 , SO 2 , CO, and C 6 H 6 ) that aligns with the results reported in other international cities and metropolitan areas. However, particulate matter (PM 10 and PM 2.5 ) averaged concentrations followed a markedly different trend from the gaseous pollutants, indicating a larger influence from natural events (sand and dust storms) and other anthropogenic sources. The ozone (O 3 ) levels increased during the lockdown, showing the complexity of O 3 formation. The end of lockdown led to an increase of the mobility and the air pollution; however, air pollutant concentrations remained in lower levels than during the same period of 2019. The results in this study show the large impact of human activities on the quality of air and present an opportunity for policymakers and decision-makers to design stimulus packages to overcome the economic slow-down, with strategies to accelerate the transition to resilient, low-emission economies and societies more connected to the nature that protect human health and the environment.

Application of remote sensing for salinity based coastal land use zoning in Bangladesh - Md. Manjur Morshed; Showmitra Kumar Sarkar; Md. Rashed Uz Zzaman; Md. Mazharul Islam (Spatial Information Research, 2021)

Electrical characterization of phytoplankton suspensions using impedance spectroscopy - Margaret R. Jett; Mohamed Z. Rashed; Susan P. Hendricks; Stuart J. Williams (Journal of Applied Phycology, 2021)

Bioenvironmental Trace Elements in Warm Climatic Plant, Pigeon Pea (Cajanus cajan) - M.Nageeb Rashed (Biological Trace Element Research, 2021)

Treatment of hepatitis C virus infection with direct-acting antivirals plus ribavirin eliminates viral RNA from peripheral blood mononuclear cells and reduces virologic relapse in diverse hepatic parenchymal changes - Mohamed Darwish Ahmed Abd Alla; Reham M. Dawood; Hassan Abd EL-Hafeth Rashed; Galal Farrag; Islam Abdelmawla Emran Ammar; Mohamed Mahmoud Abdel-Halim Mahmoud; Ghada M. Salum; Ahmed Mohamed Abdulhamid Altanbouly; Mai A. El Meguid; Mostafa K. El Awady (Archives of Virology, 2021)

The role of private sector in the implementation of sustainable development goals - Abdulkarim Hasan Rashed; Afzal Shah (Environment, Development and Sustainability, 2021)

Plio-Pleistocene to Recent tectonostratigraphic evolution of the Lalmai anticline in the western Indo-Burman Range (Bangladesh): insights from lithofacies analysis and structural synthesis - Rashed Abdullah; Abu Sadat Md Sayem; Rumana Yeasmin; Mohammad Mashiur Rahman; Zahidul Bari; Farida Khanam (Arabian Journal of Geosciences, 2021)

Model-Based Inversion of Rayleigh Wave Dispersion Curves Via Linear and Nonlinear Methods - Rashed Poormirzaee; Iztok Fister Jr (Pure and Applied Geophysics, 2021)

Autonomic and enteric function profiling can predict disordered gastric emptying in diabetic gastropathy - Hamza Hassan; Surosree Ganguli; Hani Rashed; William Johnson; Bikash Bhandari; Thomas Abell (Medical & Biological Engineering & Computing, 2021)

Sedimentology and basin-fill history of the Cenozoic succession of the Sylhet Trough, Bengal Basin, Bangladesh - Farida Khanam; M. Julleh Jalalur Rahman; M. Mustafa Alam; Rashed Abdullah (International Journal of Earth Sciences, 2021)

Development of potential map for groundwater abstraction in the northwest region of Bangladesh using RS-GIS-based weighted overlay analysis and water-table-fluctuation technique - Sara Nowreen; Imran Hossain Newton; Rashed Uz Zzaman; A. K. M. Saiful Islam; G. M. Tarekul Islam; Md. Saiful Alam (Environmental Monitoring and Assessment, 2021)

A brief outline of respiratory viral disease outbreaks: 1889–till date on the public health perspectives - Rashed Noor; Syeda Muntaka Maniha (VirusDisease, 2020)

Sulfated polysaccharide ascophyllan from Padina tetrastromatica enhances healing of burn wounds by ameliorating inflammatory responses and oxidative damage - Mohsin Sulaiman; Salem Rashed Alyileili; Mahadevan Raghavankutty; G. Muraleedhara Kurup (Molecular Biology Reports, 2020)

Molecular and hormonal changes caused by long-term use of high dose pregabalin on testicular tissue: the role of p38 MAPK, oxidative stress and apoptosis - Sarah Hamed N. Taha; Hala Saied Zaghloul; Abla Abd El Rahman Ali; Laila Ahmed Rashed; Rania Mohamed Sabry; Iman Fawzy Gaballah (Molecular Biology Reports, 2020)

In silico characterization and expression of disease-resistance-related genes within the collinear region of Brassica napus blackleg resistant locus LepR1′ in B. oleracea - Mostari Jahan Ferdous; Mohammad Rashed Hossain; Jong-In Park; Hoy-Taek Kim; Arif Hasan Khan Robin; Sathishkumar Natarajan; Manosh Kumar Biswas; Hee-Jeong Jung; Ill-Sup Nou (Journal of General Plant Pathology, 2020)

In-silico identification and differential expression of putative disease resistance-related genes within the collinear region of Brassica napus blackleg resistance locus LepR2’ in Brassica oleracea - Mohammad Rashed Hossain; Mostari Jahan Ferdous; Jong-In Park; Arif Hasan Khan Robin; Sathishkumar Natarajan; Hee-Jeong Jung; Hoy-Taek Kim; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)
Blackleg disease, caused by Leptosphaeria maculans, greatly affects the production of cabbage ( Brassica oleracea ). However, definitive R-gene(s) are yet to be identified in this crop. In contrast, a number of R-loci have been identified in A- or B-genome crops. Identification of few resistant cabbage genotypes indicates the presence of R-genes in this C-genome crop. High ancestral synteny between Brassica genomes suggests that the collinear regions of known A- or B-genome R-loci may also contain functional R-genes in the C-genome. Strong resistance was observed in the cotyledons of cabbage inbred line SCNU-98 against two L. maculans isolates, 03–02 s and 00–100 s. We investigated the collinear region of the Brassica napus blackleg resistance locus LepR2’ in B. oleracea since both isolates of L. maculans contain corresponding avirulence genes. The locus was collinear to a 5.8 Mbp genomic segment of B. oleracea chromosome C09 containing 13 genes that have putative disease resistance-related domains. High expression of genes Bo9g117290 and Bo9g111510 against isolate 00–100 s, and high expression of genes Bo9g126150 and Bo9g111490 against both isolates in the resistant-line SCNU-98 indicate their putative roles in blackleg resistance, which remained to be functionally verified. This work enhances our understanding of R-gene-mediated resistance to blackleg in cabbage.

The neurotoxic effect of long-term use of high-dose Pregabalin and the role of alpha tocopherol in amelioration: implication of MAPK signaling with oxidative stress and apoptosis - Sarah Hamed N. Taha; Hala Saied Zaghloul; Abla Abd El Rahman Ali; Iman Fawzy Gaballah; Laila Ahmed Rashed; Basma Emad Aboulhoda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Repurposing of Secukinumab as Neuroprotective in Cuprizone-Induced Multiple Sclerosis Experimental Model via Inhibition of Oxidative, Inflammatory, and Neurodegenerative Signaling - Amany El-Shahawy Abdel-Maged; Amany M. Gad; Laila Ahmed Rashed; Samar S. Azab; Eman A. Mohamed; Azza S. Awad (Molecular Neurobiology, 2020)

Unconfined Compressive Strength (UCS) and Compressibility Indices Predictions from Dynamic Cone Penetrometer Index (DCP) for Cohesive Soil in Kurdistan Region/Iraq - Younis M. Alshkane; Kamal Ahmad Rashed; Hyam Saleh Daoud (Geotechnical and Geological Engineering, 2020)

Highly effective surface modification using plasma technologies toward green coloration of polyester fabrics - Fatma Abdelghaffar; Rehab A. Abdelghaffar; Usama M. Rashed; Hend M. Ahmed (Environmental Science and Pollution Research, 2020)

The Upregulation of hsa-mir-181b-1 and Downregulation of Its Target CYLD in the Late-Stage of Tumor Progression of Breast Cancer - Alireza Andalib; Shadi Rashed; Moein Dehbashi; Jamshid Hajati; Farshid Noorbakhsh; Mazdak Ganjalikhani-Hakemi (Indian Journal of Clinical Biochemistry, 2020)

Imaging contamination surrounding a wastewater dumpsite using 2 terrain conductivity meters - Mohamed A. Rashed; Hussein M. Harbi; Burhan A. Niyazi; Ali H. Atef (Arabian Journal of Geosciences, 2020)

TP53 genetic polymorphisms and susceptibility to cervical cancer in Bangladeshi women: a case–control study - Mohd Nazmul Hasan Apu; A. Z. M. Rashed; Tafsir Bashar; Md Morshadur Rahman; Md Shaki Mostaid (Molecular Biology Reports, 2020)

Effects of Potato Psyllid Vector Density and Time of Infection on Zebra Chip Disease Development after Harvest and during Storage - Erik J. Wenninger; Nora Olsen; Jeffrey Lojewski; Phillip Wharton; Jennifer Dahan; Arash Rashed; Alexander V. Karasev (American Journal of Potato Research, 2020)
“ Candidatus Liberibacter solanacearum” (Lso) (=“ Candidatus Liberibacter psyllarous”) is an uncultured, phloem-limited bacterium that is associated with zebra chip disease (ZC) in potato ( Solanum tuberosum L.) and transmitted by the potato psyllid ( Bactericera cockerelli (Šulc)). Vector density and timing of infection have been shown to affect ZC prevalence at harvest; however, little work has been done on disease development during storage. Here we confirm with field-cage trials that ZC prevalence at harvest was greater with increased time between inoculation and vine kill. Moreover, we show that with Pacific Northwest growing conditions, ZC can develop over time during storage. Plants inoculated 2 to 3 weeks before vine kill showed little or no ZC symptoms in tubers at harvest, but higher prevalence of symptoms after 3 months in storage. For plants inoculated at 4 to 5 weeks before vine kill, tubers exhibited notable symptoms at harvest, but still showed evidence of symptom development after storage. Plants inoculated within 1 week before vine kill exhibited little or no risk of ZC in tubers at harvest or after storage. Higher vector density tended to contribute to ZC prevalence, but was far less important than timing of infection. These results underscore the potential danger of underestimating ZC prevalence at harvest for tubers being stored long term, and suggest that plants at risk of Lso infection should be protected from potato psyllids until at least 2 weeks before vine kill.

Effects of nitrite graded doses on hepatotoxicity and nephrotoxicity, histopathological alterations, and activation of apoptosis in adult rats - Nagla A. El-Nabarawy; Ahmed S. Gouda; Mohamed A. Khattab; Laila A. Rashed (Environmental Science and Pollution Research, 2020)

Migration and Household Adaptation in Climate-Sensitive Hotspots in South Asia - Amina Maharjan; Ricardo Safra de Campos; Chandni Singh; Shouvik Das; Arjun Srinivas; Mohammad Rashed Alam Bhuiyan; Sultan Ishaq; Muhammad Awais Umar; Tanzina Dilshad; Krity Shrestha; Suruchi Bhadwal; Tuhin Ghosh; et al. (Current Climate Change Reports, 2020)
Purpose of Review South Asia is highly vulnerable to the impacts of climate change, owing to the high dependency on climate-sensitive livelihoods and recurrent extreme events. Consequently, an increasing number of households are adopting labour migration as a livelihood strategy to diversify incomes, spread risks, and meet aspirations. Under the Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA) initiative, four research consortia have investigated migration patterns and their inherent linkages to adaptation to climate change in climate hotspots. This article synthesizes key findings in regional context of South Asia. Recent Findings The synthesis suggests that in climate-sensitive hotspots, migration is an important livelihood diversification strategy and a response to various risks, including climate change. Typically, one or more household members, often young men, migrated internally or internationally to work in predominantly informal sectors. Remittances helped spatially diversify household income, spread risks, and insure against external stressors. The outcomes of migration are often influenced by who moves, where to, and what capacities they possess. Summary Migration was found to help improve household adaptive capacity, albeit in a limited capacity. Migration was mainly used as a response to risk and uncertainty, but with potential to have positive adaptation co-benefits.

Modeling aquifer storage and recovery potential for seasonal water storage in the Flemish alluvial plains of Belgium using MODFLOW - Mohammad Rashed Wasif; Mohammad Mehedi Hasan (Arabian Journal of Geosciences, 2020)

Molecular characterization of Acidovorax citrulli strain NIHHS15-280 causing bacterial fruit blotch disease in Korea and screening of resistance sources in melon - Md. Rafiqul Islam; Mohammad Rashed Hossain; Hoy-Taek Kim; Ujjal Kumar Nath; Md. Abuyusuf; Hee-Jeong Jung; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)

Exercise enhances the effectiveness of vitamin D therapy in rats with Alzheimer’s disease: emphasis on oxidative stress and inflammation - Engy Medhat; Laila Rashed; Marwa Abdelgwad; Basma Emad Aboulhoda; Mohamed Mansour Khalifa; Shimaa Saad El-Din (Metabolic Brain Disease, 2020)

RETRACTED ARTICLE: Amelioration of thioacetamide-induced hepatic encephalopathy in rats by low-dose gamma irradiation - Mona Abd El-Latif El-Ghazaly; Engy Refaat Rashed; Ghada Mahmoud Shafey; Hala Fahmy Zaki; Amina Salem Attia (Environmental Science and Pollution Research, 2020)

Isolation, identification and characterization of endophytic bacteria antagonistic to Phytophthora palmivora causing black pod of cocoa in Malaysia - Wael Alsultan; Ganesan Vadamalai; Ahmad Khairulmazmi; Halimi Mohd Saud; Abdullah M. Al-Sadi; Osamah Rashed; Ahmad Kamil Mohd Jaaffar; Abbas Nasehi (European Journal of Plant Pathology, 2019)

MicroRNA as a prognostic biomarker for survival in childhood acute lymphoblastic leukemia: a systematic review - Wafaa M. Rashed; Mahmoud M. Hamza; Marwa Matboli; Sherin I. Salem (Cancer and Metastasis Reviews, 2019)

Pediatric diffuse intrinsic pontine glioma: where do we stand? - Wafaa M. Rashed; Eslam Maher; Mohamed Adel; Ossama Saber; Mohamed Saad Zaghloul (Cancer and Metastasis Reviews, 2019)

Reservoir compartmentalization phenomenon for lower Safa Reservoir, Obaiyed Gas Field, North Western Desert, Egypt - Tharwat Ahmed Abdel-Fattah; Mohamed Ahmed Rashed; Ahmed Ibrahim Diab (Arabian Journal of Geosciences, 2019)

Rutin inhibits carfilzomib-induced oxidative stress and inflammation via the NOS-mediated NF-κB signaling pathway - Naif O. Al-Harbi; Faisal Imam; Mohammed M. Al-Harbi; Othman A. Al-Shabanah; Moureq Rashed Alotaibi; Homood M. As Sobeai; Muhammad Afzal; Imran Kazmi; Ammar Cherkess Al Rikabi (Inflammopharmacology, 2019)

Preparation and Characterization of Biomass Carbon–Based Solid Acid Catalysts for the Esterification of Marine Algae for Biodiesel Production - Azeem Rana; Mohammed S. M. Alghazal; Mohammed M. Alsaeedi; Rashed S. Bakdash; Chanbasha Basheer; Abdulaziz A. Al-Saadi (BioEnergy Research, 2019)

Epidemiological assessment of clinical poultry cases through the government veterinary hospital-based passive surveillance system in Bangladesh: a case study - Md. Ashiqur Rahman; Md. Mahbubur Rahman; Md. Sadeque Abdullah; Md. Abu Sayeed; Md. Harun Rashid; Rashed Mahmud; Joseph P. Belgrad; Md. Ahasanul Hoque (Tropical Animal Health and Production, 2019)

Anticoccidial and antioxidant effects of plants derived polyphenol in broilers exposed to induced coccidiosis - Rashed A. Alhotan; Alaeldein Abudabos (Environmental Science and Pollution Research, 2019)

Development of a PCR test for detection of Xanthomonas campestris pv. raphani - Mehede Hassan Rubel; Mohammad Rashed Hossain; Ujjal Kumar Nath; Sathishkumar Natarajan; Ji-Hee Lee; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Australasian Plant Pathology, 2019)

Geotechnical performance of sandy bricks made with fine aggregates of sand dunes, Saudi Arabia - El-Sayed Sedek Abu Seif; Abdullah Rashed Sonbul (Arabian Journal of Geosciences, 2019)

BEM for thick plates on unilateral Winkler springs - Ahmed Fady Farid; Youssef F. Rashed (Innovative Infrastructure Solutions, 2018)

Spatiotemporal trends in freshwater availability in the Red Sea Hills, Saudi Arabia - Burhan A. Niyazi; Mohamed Ahmed; Jalal M. Basahi; Milad Z. Masoud; Mohamed A. Rashed (Arabian Journal of Geosciences, 2018)

Characterizing Zebra Chip Symptom Severity and Identifying Spectral Signatures Associated with ‘Candidatus Liberibacter solanacearum’-Infected Potato Tubers - Zhiguo Zhao; Sean M. Prager; Regina K. Cruzado; Xi Liang; William R. Cooper; Gongshe Hu; Arash Rashed (American Journal of Potato Research, 2018)

Active hydrothermal fluids circulation triggering small-scale collapse events: the case of the 2001–2002 fissure in the Lakki Plain (Nisyros Island, Aegean Sea, Greece) - Stefania Venturi; Franco Tassi; Orlando Vaselli; Georges E. Vougioukalakis; Heba Rashed; Christos Kanellopoulos; Chiara Caponi; Francesco Capecchiacci; Jacopo Cabassi; Andrea Ricci; Luciano Giannini (Natural Hazards, 2018)

Comparison of various drought indices to monitor drought status in Pakistan - Shahzada Adnan; Kalim Ullah; Li Shuanglin; Shouting Gao; Azmat Hayat Khan; Rashed Mahmood (Climate Dynamics, 2018)

Adaptive boxcar background filtering for real-time GPR utility detection - Ali Atef; Hussein Harbi; Mohamed Rashed (Arabian Journal of Geosciences, 2018)

Physical Clogging of Uniformly Graded Porous Media Under Constant Flow rates - Omed S. Q. Yousif; Moses Karakouzian; Nawzad O. A. Rahim; Kamal A. Rashed (Transport in Porous Media, 2017)

Subcellular Parkinson’s Disease-Specific Alpha-Synuclein Species Show Altered Behavior in Neurodegeneration - Rashed Abdullah; Ketan S. Patil; Benjamin Rosen; Ramavati Pal; Shubhangi Prabhudesai; Sungsu Lee; Indranil Basak; Esthelle Hoedt; Peter Yang; Keith Panick; Hsin-Pin Ho; Emmanuel Chang; et al. (Molecular Neurobiology, 2017)

Kinetic characterization of the inhibition of protein tyrosine phosphatase-1B by Vanadyl (VO2+) chelates - Jason Hon; Michelle S. Hwang; Meara A. Charnetzki; Issra J. Rashed; Patrick B. Brady; Sarah Quillin; Marvin W. Makinen (JBIC Journal of Biological Inorganic Chemistry, 2017)

Climate change and variability impacts on the forests of Bangladesh – a diagnostic discussion based on CMIP5 GCMs and ENSO - Md. Rashed Chowdhury; Ousmane Ndiaye (International Journal of Climatology, 2017)
The aim of this study is to assess the evolution of forests in Bangladesh from the perspective of changing climate, with particular emphasis on the Sundarbans, the world's largest mangrove forest. Projections for temperature and rainfall change have been made using the latest Intergovernmental Panel on Climate Change‐Fifth Assessment Report ( IPCC‐AR5 ) general circulation models ( GCMs ) protocol (Coupled Model Intercomparison Project Phase 5, CMIP5 ) with 38 various GCMs and up to 105 model runs. The GCMs findings were verified by the published results of 11 regional climate models ( RCMs ) in the Coordinated Regional Climate Downscaling Experiment ( CORDEX )‐South Asia models with finer spatial resolution. A CMIP5 model‐based synthesis review on the future variability of El Niño‐Southern Oscillation ( ENSO ) has also been made, as both the seasonal temperature and rainfall variability in Bangladesh are correlated to ENSO . Both global and regional climate change scenarios indicate that temperature would continue to rise and total annual rainfall is likely to increase in the future. However, weak increases in rainfall combined with high increases in temperature would create a high demand and competition for water because of the higher evapotranspiration environment. In addition to changing climate, the interannual variability of ENSO would further aggravate problems because it displays important correlations with the variability of rainfall, temperatures, sea‐level, lightning, and forest fires in Bangladesh. This study strongly recommends that future climate change projections should be combined with interannual variability ENSO to improve climate perspectives for stronger forest capacity building efforts in Bangladesh.

Molecular factors regulating E-cadherin expression in urothelial bladder cancer and their correlations with the clinicopathological features - Samia Hussein; Hala Mosaad; Hayam E. Rashed; Shimaa Ahmed; Ahmed Ragab; Eman I. Ismail (Molecular Biology Reports, 2017)

Effects of Holding Temperatures on the Development of Zebra Chip Symptoms, ‘Candidatus Liberibacter Solanacearum’ Titers, and Phenolic Levels in ‘Red La Soda’ and ‘Russet Norkotah’ Tubers - C. M. Wallis; A. Rashed; F. Workneh; L. Paetzold; C. M. Rush (American Journal of Potato Research, 2017)

ECG imaging of ventricular tachycardia: evaluation against simultaneous non-contact mapping and CMR-derived grey zone - Walther H. W. Schulze; Zhong Chen; Jatin Relan; Danila Potyagaylo; Martin W. Krueger; Rashed Karim; Manav Sohal; Anoop Shetty; YingLiang Ma; Nicholas Ayache; Maxime Sermesant; Herve Delingette; et al. (Medical & Biological Engineering & Computing, 2017)

Sugar beet wireworm Limonius californicus damage to wheat and barley: evaluations of plant damage with respect to soil media, seeding depth, and diatomaceous earth application - Arash Rashed; Christopher W. Rogers; Mahnaz Rashidi; Juliet M. Marshall (Arthropod-Plant Interactions, 2017)

Aryl hydrocarbon receptor (AhR) rs2066853 gene polymorphism association with infertile oligoasthenoteratozoospermic men and seminal oxidative stress - Taymour Mostafa; Hanan Fouad; Nashaat Nabil; Laila Rashed; Dina Sabry; Khadiga Abougabal; Bolis S. Gendy (Environmental Science and Pollution Research, 2017)

Projecting South Asian summer precipitation in CMIP3 models: A comparison of the simulations with and without black carbon - Shuanglin Li; Rashed Mahmood (Journal of Meteorological Research, 2017)

Experimental assessment of non-edible candlenut biodiesel and its blend characteristics as diesel engine fuel - H. K. Imdadul; N. W. M. Zulkifli; H. H. Masjuki; M. A. Kalam; M. Kamruzzaman; M. M. Rashed; H. K. Rashedul; Azham Alwi (Environmental Science and Pollution Research, 2017)

S-wave velocity profiling from refraction microtremor Rayleigh wave dispersion curves via PSO inversion algorithm - Rashed Poormirzaee (Arabian Journal of Geosciences, 2016)

First Record of Porpita porpita (Cnidaria: Hydrozoa) from the coral reef ecosystem, Bangladesh - M. Shah Nawaz Chowdhury; S. M. Sharifuzzaman; Sayedur Rahman Chowdhury; Md. Rashed-Un-Nabi; M. Shahadat Hossain (Ocean Science Journal, 2016)

Adsorptive removal of Cu(II) and Pb(II) onto mixed-waste activated carbon: kinetic, thermodynamic, and competitive studies and application to real wastewater samples - Zeid Abdullah ALOthman; Mohamed Abdelaty Habila; Nora H. Al-Shalan; Sulaiman M. Alfadul; Rahmat Ali; Ibrahim Gar Al alm Rashed; Bader Alfarhan (Arabian Journal of Geosciences, 2016)

Environmental challenges of trans-boundary water resources management: the case of Bangladesh - Mohammed Abdul Baten; Rashed Al Mahmud Titumir (Sustainable Water Resources Management, 2016)

Diabetes-induced changes in the morphology and nociceptinergic innervation of the rat uterus - Saeed Tariq; Syed M. Nurulain; Hameed Rashed; Mohamed Lotfy; Starling Bright Emerald; Surya Koturan; Kornélia Tekes; Ernest Adeghate (Journal of Molecular Histology, 2016)

Conjugate Heat Transfer in an Annulus with Porous Medium Fixed Between Solids - Irfan Anjum Badruddin; Salman Ahmed N. J.; Abdullah A. A. A. Al-Rashed; N. Nik-Ghazali; Mohammed Jameel; Sarfaraz Kamangar; H. M. T. Khaleed; T. M. Yunus Khan (Transport in Porous Media, 2015)

Evidence of Salicylic Acid-Mediated Protein Degradation and Amino Acid Transport in Mature Leaves of Brassica napus - Qian Zhang; Bok-Rye Lee; Sang-Hyun Park; Rashed Zaman; Dong-Won Bae; Tae-Hwan Kim (Journal of Plant Growth Regulation, 2015)

Inversion seismic refraction data using particle swarm optimization: a case study of Tabriz, Iran - Rashed Poormirzaee; Rasoul Hamidzadeh Moghadam; Ahmad Zarean (Arabian Journal of Geosciences, 2015)

Modification of Hippocampal Markers of Synaptic Plasticity by Memantine in Animal Models of Acute and Repeated Restraint Stress: Implications for Memory and Behavior - Shaimaa Nasr Amin; Ahmed Amro El-Aidi; Mohamed Mostafa Ali; Yasser Mahmoud Attia; Laila Ahmed Rashed (NeuroMolecular Medicine, 2015)

Mapping underground utilities within conductive soil using multi-frequency electromagnetic induction and ground penetrating radar - Mohamed Rashed; Ali Atef (Arabian Journal of Geosciences, 2015)

The effect of glucagon-like peptide-1 in the management of diabetes mellitus: cellular and molecular mechanisms - Mohamed Lotfy; Jaipaul Singh; Hameed Rashed; Saeed Tariq; Erika Zilahi; Ernest Adeghate (Cell and Tissue Research, 2014)

Fifty years of stacking - Mohamed Rashed (Acta Geophysica, 2014)

An improved sea level forecasting scheme for hazards management in the US ‐affiliated Pacific Islands - Md. Rashed Chowdhury; Pao‐Shin Chu; Charles Chip Guard (International Journal of Climatology, 2014)
This study describes an improved seasonal sea level forecasting scheme by the Pacific ENSO Applications Climate Center ( PEAC ). Since 2005, an operational sea level forecasting scheme (3–5 months in advance) for the US‐affiliated Pacific Islands ( USAPI ) has been instrumental ( http://www.prh.noaa.gov/peac/sea‐level.php ). The El Niño‐Southern Oscillation ( ENSO ) climate cycle and the sea‐surface temperatures ( SSTs ) in the tropical Pacific Ocean are taken as the primary factors in modulating these forecasts on seasonal time scales. The current SST ‐based canonical correlations analysis ( CCA ) hindcast forecasts have been found to be skillful. However, the skill gradually decreases as the lead‐time increases. This has motivated us to revisit the forecasting scheme at PEAC . In contrast to previous endeavours which relied only on SSTs , we now incorporate both trade winds and SSTs for modulating sea level variability on seasonal time scales. The average forecasts for zero to three seasons' lead‐times are found to be 0.647, 0.598, and 0.625 for combined SST and the zonal component of the trade wind (U), SST , and wind (U), respectively. It is therefore revealed that the combined SST‐wind‐based forecasts are more skillful than the SST or wind‐based forecasts alone. It is particularly more efficient on longer time scales for most of the stations (e.g. 10–25% improvement on two to three seasons' lead‐times). The improvements of these forecasts have enabled the capability of our clients in the USAPI region to develop a more efficient long‐term response plan for hazard management.

Geophysical Constraints on the Hydrogeologic and Structural Settings of the Gulf of Suez Rift-Related Basins: Case Study from the El Qaa Plain, Sinai, Egypt - Mohamed Ahmed; William Sauck; Mohamed Sultan; Eugene Yan; Farouk Soliman; Mohamed Rashed (Surveys in Geophysics, 2014)

Inhibitory activities of three Malaysian edible seaweeds on lipase and α-amylase - Vimala Balasubramaniam; Suraiami Mustar; Norhayati Mustafa Khalid; Aswir Abd Rashed; Mohd Fairulnizal Mohd Noh; Matthew D. Wilcox; Peter I. Chater; Iain A. Brownlee; Jeffrey P. Pearson (Journal of Applied Phycology, 2013)

On the application of GPR for locating underground utilities in urban areas - Mohamed A. Rashed; Mansour A. Al-Garni (Arabian Journal of Geosciences, 2013)

Application of Analytic Signal and Euler Deconvolution in Archaeo-Magnetic Prospection for Buried Ruins at the Ancient City of Pelusium, NW Sinai, Egypt: A Case Study - Akram Mekhael Aziz; William August Sauck; El-Arabi Hendi Shendi; Mohamed Ahmed Rashed; Mohamed Abd El-Maksoud (Surveys in Geophysics, 2013)

Petrology, geochemistry and remote sensing data of island arc assemblage along Wadi Abu Marawat, Central Eastern Desert, Egypt - A. M. Asran; R. Kh. Bekir; E. Abdel Rahman; A. Abdel El-Rashed (Arabian Journal of Geosciences, 2013)

Delay in the onset of South Asian summer monsoon induced by local black carbon in an AGCM - Rashed Mahmood; Shuanglin Li (Theoretical and Applied Climatology, 2013)

Epidemiology and potential associated risk factors of drug-related problems in hospitalised children in the United Kingdom and Saudi Arabia - Asia N. Rashed; Antje Neubert; Stephen Tomlin; John Jackman; Hani Alhamdan; Adnan AlShaikh; Ahmed Attar; Mohammed Aseeri; Lynda Wilton; Ian C. K. Wong (European Journal of Clinical Pharmacology, 2012)

Risk factors associated with adverse drug reactions in hospitalised children: international multicentre study - Asia N. Rashed; Ian C. K. Wong; Noel Cranswick; Stephen Tomlin; Wolfgang Rascher; Antje Neubert (European Journal of Clinical Pharmacology, 2012)

Effect of recombinant erythropoietin on ischemia–reperfusion-induced apoptosis in rat liver - Heba M. Shawky; Sandra M. Younan; Leila A. Rashed; Heba Shoukry (Journal of Physiology and Biochemistry, 2012)

Analysis of Heat and Mass Transfer in a Vertical Annular Porous Cylinder Using FEM - Irfan Anjum Badruddin; N. J. Salman Ahmed; Abdullah A. A. A. Al-Rashed; Jeevan Kanesan; Sarfaraz Kamangar; H. M. T. Khaleed (Transport in Porous Media, 2012)

Sediments deposition due to soil erosion in the watershed region of Mangla Dam - Mohsin Jamil Butt; Rashed Mahmood; Ahmad Waqas (Environmental Monitoring and Assessment, 2011)

Temporal and spatial distribution of fish and shrimp assemblage in the Bakkhali river estuary of Bangladesh in relation to some water quality parameters - Md. Rashed-Un-Nabi; Md. Abdulla Al-Mamun; Md. Hadayet Ullah; M. Golam Mustafa (Marine Biology Research, 2011)

Background matching behaviour and pathogen acquisition: plant site preference does not predict the bacterial acquisition efficiency of vectors - Arash Rashed; Nabil Killiny; Joyce Kwan; Rodrigo P. P. Almeida (Arthropod-Plant Interactions, 2011)

Use of spectral analysis for detection of alterations in ETM data, Yazd, Iran - Rashed Poormirzaee; Majid Mohammady Oskouei (Applied Geomatics, 2010)

The Combined Effect of Vegetation and Soil Erosion in the Water Resource Management - Mohsin Jamil Butt; Ahmad Waqas; Rashed Mahmood (Water Resources Management, 2010)

Effects of streptozotocin-induced long-term diabetes on parietal cell function and morphology in rats - Salim M. A. Bastaki; Ernest Adeghate; Irwin S. Chandranath; Naheed Amir; Saeed Tariq; Rashed S. Hameed; Abdu Adem (Molecular and Cellular Biochemistry, 2010)

Screening for tetracycline residues in food products of animal origin in the State of Kuwait using Charm II radio-immunoassay and LC/MS/MS methods - Hani M. Al-Mazeedi; Alaa B. Abbas; Hussam F. Alomirah; Wafaa Y. Al-Jouhar; Siham A. Al-Mufty; Mohamed M. Ezzelregal; Rashed A. Al-Owaish (Food Additives & Contaminants: Part A, 2010)

Sea level extremes in the U.S.-Affiliated Pacific Islands—a coastal hazard scenario to aid in decision analyses - Md. Rashed Chowdhury; Pao-Shin Chu; Xin Zhao; Thomas A. Schroeder; John J. Marra (Journal of Coastal Conservation, 2010)

Neuropsychiatric evaluation of patients with brucellosis - Ghaydaa A. Shehata; Laila Abdel-Baky; Heba Rashed; Hussein Elamin (Journal of NeuroVirology, 2010)

Gastroprotective and antisecretory effects of Ailanthus excelsa (Roxb) - Larissa S. Melanchauski; Ana Paula G. S. Broto; Thiago M. Moraes; Ana Lúcia M. Nasser; Ataa Said; Usama W. Hawas; Khaled Rashed; Wagner Vilegas; Clélia A. Hiruma-Lima (Journal of Natural Medicines, 2010)

Variability and predictability of sea-level extremes in the Hawaiian and U.S.-Trust Islands—a knowledge base for coastal hazards management - Md. Rashed Chowdhury; P.-S. Chu; Thomas A. Schroeder; Xin Zhao (Journal of Coastal Conservation, 2008)

Seasonal sea‐level forecasts by canonical correlation analysis—an operational scheme for the U.S.‐affiliated Pacific Islands - MD. Rashed Chowdhury; Pao‐Shin Chu; Thomas Schroeder; Nicole Colasacco (International Journal of Climatology, 2007)
The objective of this study is to develop an operational canonical correlation analysis (CCA) statistical model for sea‐level forecasts in the U. S.‐affiliated Pacific Islands (USAPI) with lead times of several months or longer. The El Niño‐Southern Oscillation (ENSO) climate cycle and the sea‐surface temperatures (SSTs) in the tropical Pacific Ocean are taken as the primary factors in modulating sea‐level variability on the seasonal time scales. Observations revealed that the sea‐level variations in the USAPI are sensitive to ENSO cycle with low sea level during El Niño and high sea level during La Niña events. The correlation between the sea‐level variability and the fluctuations of tropical Pacific SSTs has been found to be strong. The cross‐validated results indicated that the SST‐based CCA model is potentially useful in predicting seasonal sea‐level variations in the USAPI. For all target seasons at 1‐ and 2‐season lead times, the average correlation skill has been found to be 0.50 or better. Based on this operational CCA model, the real‐time forecasts for seasonal sea‐level variations (i.e. deviations with respect to climatology) are published at the official web site of Pacific ENSO Applications Center (PEAC) ( http://lumahai.soest.hawaii.edu/Enso/peu/update.html ) for planning and decision options regarding hazard management in the USAPI. Copyright © 2007 Royal Meteorological Society

Fruit Stones from Industrial Waste for the Removal of Lead Ions from Polluted Water - M. N. Rashed (Environmental Monitoring and Assessment, 2006)

Animal Hair as Biological Indicator for Heavy Metal Pollution in Urban and Rural Areas - M. Nageeb Rashed; M. E. Soltan (Environmental Monitoring and Assessment, 2005)

Multiple dolomitization events of the Lower Carboniferous Um Bogma Formation, west central Sinai, Egypt - M. N. Shaaban; H. M. Holail; K. N. Sedeik; M. A. Rashed (Carbonates and Evaporites, 2005)

Consensus Seasonal Flood Forecasts and Warning Response System (FFWRS): An Alternate for Nonstructural Flood Management in Bangladesh - MD. Rashed Chowdhury (Environmental Management, 2005)

Hydro‐meteorological variability in the greater Ganges–Brahmaputra–Meghna basins - MD. Rashed Chowdhury; Neil Ward (International Journal of Climatology, 2004)
The flows of the Ganges, Brahmaputra and Meghna (GBM) are highly seasonal, and heavily influenced by monsoon rainfall. As a result, these rivers swell to their banks and often overflow during the monsoon months. This is most pronounced in the downstream regions, particularly in Bangladesh, which is the lowest riparian country. The objective of this paper is to study this hydro‐meteorological variability in the greater GBM regions, including the headwater regions in India and their role in streamflows in Bangladesh, and explore the large‐scale oceanic factors affecting this hydro‐meteorological variability. Global precipitation data, Bangladesh rainfall and streamflow records have been analysed and related to large‐scale climate patterns, including upstream rainfall, regional atmospheric circulation and patterns of sea‐surface temperature. The findings have quantified how the streamflows of these rivers in Bangladesh are highly correlated with the rainfall in the upper catchments with typically a lag of about 1 month. Therefore, streamflows in Bangladesh could be reasonably estimated for 1 to 3 months in advance (especially for the Ganges and Brahmaputra rivers) by employing simple correlation, if rainfall data from countries further up are available on a real‐time and continuous basis. In the absence of rainfall data, streamflow forecasts are still possible from unusually warm or cold sea‐surface temperatures in the tropics. The study concludes that hydro‐meteorological information flow between Bangladesh and other neighbouring countries is essential for developing a knowledge base for evaluating the potential implications of seasonal streamflow forecast in the GBM basins in Bangladesh. Copyright © 2004 Royal Meteorological Society

High‐resolution shallow seismic and ground penetrating radar investigations revealing the evolution of the Uemachi Fault system, Osaka, Japan - Mohamed Rashed; Koichi Nakagawa (Island Arc, 2004)
Ground penetrating radar (GPR) and high‐resolution shallow reflection seismic surveying were carried out to investigate the subsurface geology in and around the Uemachi Fault zone in the Yamato River area, Osaka, Japan. Shallow drilling in the area showed a major displacement event during the middle Pleistocene. The main Uemachi Fault plane could be clearly imaged on the seismic section, except for the most shallow 200 m. Several shallow normal fault planes with less displacement could be detected on both sides of the fault plane. GPR profiles confirmed the presence of several shallow normal faults within the area near the fault zone. These shallow faults could be followed in all of the GPR profiles crossing the fault zone. The integration of seismic section, GPR profiles and drilling data led to a conceptual model that explains the evolution of the Uemachi Fault system. The proposed model suggests the occurrence of several cycles of small vertical displacement along the deep part of the fault plane caused by the regional east–west compressional stress. The ductile nature of the shallow sedimentary cover and the absence of confining pressure in the shallow part allow for a considerable amount of plastic bending before failing in the shallow sedimentary layers. This bending generates stretching force within the shallow sedimentary cover, which in time, along with gravitational force, gives rise to the formation of the swarm of normal faults within the shallow layers near the fault zone. Some of the detected faults extend to a depth of less than 3 m below the ground surface, suggesting that the last tectonic activity along the fault plane may have occurred recently.

The evolution of locomotory behavior in profitable and unprofitable simulated prey - Thomas N. Sherratt; Arash Rashed; Christopher D. Beatty (Oecologia, 2004)

The Impact of `Greater Dhaka Flood Protection Project' (GDFPP) on Local Living Environment – The Attitude of the Floodplain Residents - Md. Rashed Chowdhury (Natural Hazards, 2003)

Cadmium and Lead Levels in Fish (Tilapia Nilotica) Tissues as Biological Indicator for Lake Water Pollution - M. N. Rashed (Environmental Monitoring and Assessment, 2001)

An Assessment of Flood Forecasting in Bangladesh: The Experience of the 1998 Flood - Md. Rashed Chowdhury (Natural Hazards, 2000)

Water Resources in the GCC Countries: An Overview - Muhammad F. Al-Rashed; Mohsen M. Sherif (Water Resources Management, 2000)

Dolomitization of middle miocene buildups, Um Gheig area, Red Sea coast, Egypt - Mohamed N. Shaaban; Hanafy M. Holail; Mohamed A. Rashed (Carbonates and Evaporites, 1997)

Distribution and chemical fractionation of some heavy metals in bottom sediments of Lake Nasser - S. M. N. Moalla; R. M. Awadallah; M. N. Rashed; M. E. Soltan (Hydrobiologia, 1997)